2-Propanol Fuel Cell System - Braun, Katharina; Mahayni, Yazan; Thiele, Simon; Weiß, Lukas; Wensing, Michael (EFCF 2023: Low-Temp. Fuel Cells, Electrolysers & H2 Processing, 2023)
Keywords: alternative fuel cell systems; system efficiency; thermodynamic system evaluation; steady-state 1D modeling; heat integration

30 μm thin hexamethyl-p-terphenyl poly(benzimidazolium) anion exchange membrane for vanadium redox flow batteries - Shanahan, Brian; Böhm, Thomas; Britton, Benjamin; Holdcroft, Steven; Zengerle, Roland; Vierrath, Severin; Thiele, Simon; Breitwieser, Matthias (Electrochemistry Communications, 2019)
We present the first results of an anion exchange ionomer membrane, hexamethyl-p-terphenyl poly(benzimidazolium) (HMT-PMBI), in a vanadium redox flow battery. Anion exchange membranes exhibit superior vanadium crossover suppression compared to proton exchange membranes due to the Gibbs–Donnan effect. HMT-PMBI was benchmarked against a similarly thin Nafion XL membrane which allowed us to compare differences based solely on chemical properties of the ionomer materials. We report cycling data of 45 cycles at a current density of 150 mA/cm 2 with excellent coulombic efficiency of >99.4%, energy efficiency of 80.6–74.2% and a low ohmic resistance of 0.219–0.255 Ω cm 2 . In addition, a three times lower self-discharge rate is obtained for the HMT-PMBI membrane compared to Nafion XL. HMT-PMBI is therefore a potential alternative for PFSA based ionomers in VRFB applications.
CRIS-Team Scopus Importer:2019-05-03
Keywords: Anion exchange membrane; Coulombic efficiency; Energy storage; HMT-PMBI; Vanadium redox flow battery

A comprehensive study on the ionomer properties of PFSA membranes with confocal Raman microscopy - Maier, Maximilian; Abbas, Dunia; Komma, Miriam; Solihul Mu'min, Muhammad; Thiele, Simon; Böhm, Thomas (Journal of Membrane Science, 2023)
The proton exchange membrane is the heart of many electrochemical energy systems, and their performance and longevity depend on a careful selection and processing of membrane materials. In this work, we use confocal Raman microscopy to investigate application-relevant properties of perfluorinated sulfonic acid (PFSA) membranes. Raman spectra of Nafion, Aquivion, and 3M Ionomer at different equivalent weights show differences in the spectral area and position of various Raman bands but reveal a clear trend of band intensities versus equivalent weight. Characteristics of these ionomers such as swelling and water uptake were determined with through-plane imaging. The technique offers advantages over conventional measurements, such as contact-free and non-destructive data acquisition. Calibration curves for the equivalent weight were derived for the different PFSAs with excellent linear fits that allow a quantification of the ionizable group content. The high spatial resolution of confocal Raman microscopy of less than 2 μm enables the local evaluation of all these ionomer properties. Furthermore, Raman imaging was employed to characterize composite membranes, which shows that it can resolve individual phases and features in multi-layered membranes. This study provides a comprehensive summary of confocal Raman microscopy as a powerful tool for the analysis of ionomer and membrane properties.
CRIS-Team Scopus Importer:2023-01-06
Keywords: Confocal Raman microscopy; Electrochemical energy systems; Imaging; Ionomer; Membrane

Activation of electrospun carbon fibers: the effect of fiber diameter on CO2 and steam reaction kinetics - Erben, Johannes; Heußner, Alenica; Thiele, Simon; Kerzenmacher, Sven (Journal of Polymer Research, 2021)
First, we present a fabrication process for electrospun carbon fiber mats with mean fiber diameters between 108 nm and 623 nm. The carbon fiber mats were produced by electrospinning of polyacrylonitrile (PAN) solutions and subsequent carbonization. The fiber mats feature small variations of their properties that are required for parameter studies. Second, we investigate the kinetics of steam and CO2 activation with three different activation temperatures and times. Both activation methods result in a surface area increase depending on activation temperature and time. Detailed analysis of the macroscopic properties burn-off, surface area, and conductivity reveals insights into the microscopic activation kinetics. The different fiber diameters of the carbon fiber mats enable the distinction of surface driven and bulk processes. Our results indicate, that CO2 activation kinetics are mass transport controlled, and that steam activation kinetics are reaction rate controlled. The turbostratic nature of PAN derived carbon and the distinct characteristics of the activation agents could explain the nonlinear behavior of the burn-off and surface area development.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Carbon; Electrospinning; Fabrication process; Fiber diameter; Polyacrylonitrile (PAN); Steam- and CO

Active solution heating and cooling in electrospinning enabling spinnability from various solvents - Abbas, Dunia; Mu'Min, Muhammad S.; Bonanno, Marco; Thiele, Simon; Boehm, Thomas (Journal of Applied Polymer Science, 2022)
Solution electrospinning is a facile method for the production of nanofibrous meshes. Here, we present a syringe-jacket heat exchanger as a simple add-on for solution electrospinning, which enables spinning from various solvents by a direct and precise solution temperature control between -20 degrees C and 100 degrees C. An effective manipulation of the solvent evaporation rate is enabled by adjusting the temperature. Exemplarily, we investigated the spinning of poly(vinylidene fluoride)-co-hexafluoropropylene (PVDF-HFP) in pure dimethylacetamide (DMAc) or acetone as representatives of low and highly volatile solvents. Electrospinning of these solutions is not possible at ambient conditions, either due to a too low or too high evaporation rate. However, we find that PVDF-HFP nanofibers can be successfully electrospun from DMAc at a solution temperature of 75 degrees C and from acetone at -19 degrees C. We show for the first time the use of an active solution cooling for electrospinning from a highly volatile solvent such as acetone. The ability to precisely adjust the solution temperature during electrospinning offers an improved process control and broadens the spectrum of spinnable solution compositions. Especially the prospect of replacing highly toxic solvents with less-toxic solvents such as acetone opens up a wide field of application for the produced fibers.
CRIS-Team WoS Importer:2022-06-24

A fully spray-coated fuel cell membrane electrode assembly using Aquivion ionomer with a graphene oxide/cerium oxide interlayer - Breitwieser, Matthias; Bayer, Thomas; Buechler, Andreas; Zengerle, Roland; Lyth, Stephen M.; Thiele, Simon (Journal of Power Sources, 2017)
A novel multilayer membrane electrode assembly (MEA) for polymer electrolyte membrane fuel cells (PEMFCs) is fabricated in this work, within a single spray-coating device. For the first time, direct membrane deposition is used to fabricate a PEMFC by spraying the short-side-chain ionomer Aquivion directly onto the gas diffusion electrodes. The fully sprayed MEA, with an Aquivion membrane 10 μm in thickness, achieved a high power density of 1.6 W/cm2 for H2/air operation at 300 kPaabs. This is one of the highest reported values for thin composite membranes operated in H2/air atmosphere. By the means of confocal laser scanning microscopy, individual carbon fibers from the gas diffusion layer are identified to penetrate through the micro porous layer (MPL), likely causing a low electrical cell resistance in the range of 150 Ω cm2 through the thin sprayed membranes. By spraying a 200 nm graphene oxide/cerium oxide (GO/CeO2) interlayer between two layers of Aquivion ionomer, the impact of the electrical short is eliminated and the hydrogen crossover current density is reduced to about 1 mA/cm2. The peak power density of the interlayer-containing MEA drops only by 10% compared to a pure Aquivion membrane of similar thickness.
CRIS-Team Scopus Importer:2023-03-29
Keywords: Aquivion; Cerium oxide; Direct membrane deposition; Graphene oxide; Membrane degradation; PEMFC; Spray coating

Amorphous Carbon Coatings for Total Knee Replacements—Part I: Deposition, Cytocompatibility, Chemical and Mechanical Properties - Rothammer, Benedict; Neusser, Kevin; Marian, Max; Bartz, Marcel; Krauß, Sebastian; Böhm, Thomas; Thiele, Simon; Merle, Benoit; Detsch, Rainer; Wartzack, Sandro (Polymers, 2021)
Diamond-like carbon (DLC) coatings have the potential to reduce implant wear and thus to contribute to avoiding premature failure and to increasing service life of total knee replacements (TKAs). This two-part study addresses the development of such coatings for ultrahigh molecular weight polyethylene (UHMWPE) tibial inlays as well as cobalt-chromium-molybdenum (CoCr) and titanium (Ti64) alloy femoral components. While a detailed characterization of the tribological behavior is the subject of part II, part I focusses on the deposition of pure (a-C:H) and tungsten-doped hydrogen-containing amorphous carbon coatings (a-C:H:W) and the detailed characterization of their chemical, cytological, mechanical and adhesion behavior. The coatings are fabricated by physical vapor deposition (PVD) and display typical DLC morphology and composition – as verified by focused ion beam scanning electron microscopy and Raman spectroscopy. Their roughness is higher than that of the plain substrates. Initial screening with contact angle and surface tension as well as in vitro testing by indirect and direct application indicate favorable cytocompatibility. The DLC coatings feature excellent mechanical properties with a substantial enhancement of indentation hardness and elastic modulus ratios. The adhesion of the coatings as determined in modified scratch tests can be considered as sufficient for the use in TKAs.<br
Keywords: DLC coating; Biomedical applications; Biotribology; UHMWPE; CoCr; Ti64; Total knee arthroplasty; Cytocompatibility; Hardness; Adhesion

Amorphous Carbon Coatings for Total Knee Replacements—Part II: Tribological Behavior - Rothammer, Benedict; Marian, Max; Neusser, Kevin; Bartz, Marcel; Böhm, Thomas; Krauß, Sebastian; Schroeder, Stefan; Uhler, Maximilian; Thiele, Simon; Merle, Benoit; Kretzer, J. Philippe; Wartzack, Sandro (Polymers, 2021)
Diamond-like carbon coatings may decrease implant wear, therefore, they are helping to reduce aseptic loosening and increase service life of total knee arthroplasties (TKAs). This two-part study addresses the development of such coatings for ultrahigh molecular weight polyethylene (UHMWPE) tibial inlays as well as cobalt-chromium-molybdenum (CoCr) and titanium (Ti64) alloy femoral components. While the deposition of a pure (a-C:H) and tungsten-doped hydrogen-containing amorphous carbon coating (a-C:H:W) as well as the detailed characterization of mechanical and adhesion properties were the subject of Part I, the tribological behavior is studied in Part II. Pin-on-disk tests are performed under artificial synovial fluid lubrication. Numerical elastohydrodynamic lubrication modeling is used to show the representability of contact conditions for TKAs and to assess the influence of coatings on lubrication conditions. The wear behavior is characterized by means of light and laser scanning microscopy, Raman spectroscopy, scanning electron microscopy and particle analyses. Although the coating leads to an increase in friction due to the considerably higher roughness, especially the UHMWPE wear is significantly reduced up to a factor of 49% (CoCr) and 77% (Ti64). Thereby, the coating shows continuous wear and no sudden failure or spallation of larger wear particles. This demonstrated the great potential of amorphous carbon coatings for knee replacements.
Keywords: DLC coating; Biomedical applications; Biotribology; UHMWPE; CoCr; Ti64; Total knee arthroplasty; Pin-on-disk; Friction; Wear

An Artificial SEI Layer Based on an Inorganic Coordination Polymer with Self-Healing Ability for Long-Lived Rechargeable Lithium-Metal Batteries - Beichel, Witali; Skrotzki, Julian; Klose, Petra; Njel, Christian; Butschke, Burkhard; Burger, Stephan; Liu, Lili; Thomann, Ralf; Thomann, Yi; Biro, Daniel; Thiele, Simon; Krossing, Ingo (Batteries & Supercaps, 2021)
Upon immersion of a lithium (Li) anode into a diluted 0.05 to 0.20 M dimethoxyethane solution of the phosphoric-acid derivative (CF3CH2O)(2)P(O)OH (HBFEP), an artificial solid-electrolyte interphase (SEI) is generated on the Li-metal surface. Hence, HBFEP reacts on the surface to the corresponding Li salt (LiBFEP), which is a Li-ion conducting inorganic coordination polymer. This film exhibits - due to the reversibly breaking ionic bonds - self-healing ability upon cycling-induced volume expansion of Li. The presence of LiBFEP as the major component in the artificial SEI is proven by ATR-IR and XPS measurements. SEM characterization of HBFEP-treated Li samples reveals porous layers on top of the Li surface with at least 3 pm thickness. Li-Li symmetrical cells with HBFEP-modified Li electrodes show a three- to almost fourfold cycle-lifetime increase at 0.1 mA cm(-2) in a demanding model electrolyte that facilitates fast battery failure (1 M LiOTf in TEGDME). Hence, the LiBFEP-enriched layer apparently acts as a Li-ion conducting protection barrier between Li and the electrolyte, enhancing the rechargeability of Li electrodes.
CRIS-Team WoS Importer:2021-12-24

Anion-Exchange Membrane Water Electrolyzers - Du, Naiying; Roy, Claudie; Peach, Retha; Turnbull, Matthew; Thiele, Simon; Bock, Christina (Chemical Reviews, 2022)
This Review provides an overview of the emerging concepts of catalysts, membranes, and membrane electrode assemblies (MEAs) for water electrolyzers with anion-exchange membranes (AEMs), also known as zero-gap alkaline water electrolyzers. Much of the recent progress is due to improvements in materials chemistry, MEA designs, and optimized operation conditions. Research on anion-exchange polymers (AEPs) has focused on the cationic head/backbone/side-chain structures and key properties such as ionic conductivity and alkaline stability. Several approaches, such as cross-linking, miaophase, and organic/inorganic composites, have been proposed to improve the anion-exchange performance and the chemical and mechanical stability of AEMs. Numerous AEMs now exceed values of 0.1 S/cm (at 60-80 degrees C), although the stability specifically at temperatures exceeding 60 degrees C needs further enhancement. The oxygen evolution reaction (OER) is still a limiting factor. An analysis of thin-layer OER data suggests that NiFe-type catalysts have the highest activity. There is debate on the active-site mechanism of the NiFe catalysts, and their long-term stability needs to be understood. Addition of Co to NiFe increases the conductivity of these catalysts. The same analysis for the hydrogen evolution reaction (HER) shows carbon-supported Pt to be dominating, although PtNi alloys and clusters of Ni(OH)(2) on Pt show competitive activities. Recent advances in forming and embedding well-dispersed Ru nanoparticles on functionalized high-surface-area carbon supports show promising HER activities. However, the stability of these catalysts under actual AEMWE operating conditions needs to be proven. The field is advancing rapidly but could benefit through the adaptation of new in situ techniques, standardized evaluation protocols for AEMWE conditions, and innovative catalyst-structure designs. Nevertheless, single AEM water electrolyzer cells have been operated for several thousand hours at temperatures and current densities as high as 60 degrees C and 1 A/cm(2), respectively.
CRIS-Team WoS Importer:2022-07-15

A steady-state monte carlo study on the effect of structural and operating parameters on liquid water distribution within the microporous layers and the catalyst layers of PEM fuel cells - Pournemat, A.; Wilhelm, F.; Haussmann, J.; Vierrath, S.; Thiele, Simon; Scholta, J. (Journal of The Electrochemical Society, 2018)
The distribution of liquid water agglomerations within a catalyst layer and a microporous layer of a polymer electrolyte membrane fuel cell employing a Monte Carlo model are simulated. The simulations are based on real material structures and locally resolved operating conditions. The 3D material structures are obtained from focused ion beam tomography capable of nm-scale imaging. The local temperature and the relative humidity profiles are provided by a computational fluid dynamics simulation, based on a single channel fuel cell model taking into account all relevant transport and electrochemical processes. The results of this Monte Carlo study confirm the strong dependency of the water saturation in the catalyst layer and microporous layer on the structural parameters and operating conditions, such as: wettability, pore size and local temperature and relative humidity.
CRIS-Team Scopus Importer:2023-03-29

Bipolar-interface fuel cells - an underestimated membrane electrode assembly concept for PGM-free ORR catalysts - Seeberger, Dominik; McLaughlin, David; Hauenstein, Pascal; Thiele, Simon (Sustainable Energy & Fuels, 2020)
We present the first combination of a bipolar interface fuel cell with a commercial Fe-N/C catalyst as an alkaline cathode and a PGM-based, acidic anode, both separated by a proton exchange membrane (PEM). This membrane electrode assembly (MEA) concept enables the employment of Fe-N/C catalysts in a less corrosive alkaline environment, while simultaneously keeping the profound advantages of the hydrogen oxidation reaction in acidic media with extremely low PGM-material requirement. We compare two different cases for the anion exchange polymer-proton exchange polymer (AEM|PEM) interface at the alkaline cathode and the acidic membrane. In one case the PEM is simply pressed against the alkaline electrode and in the other case a part of the PEM is deposited onto the alkaline electrode. We achieved power densities of about 38 mW cm−2and 210 mW cm−2respectively. This is corresponding to 2.1 W mgPt−1cm−2. Our results show, that the bipolar interface design is one of the most important factors for performance optimization in BPM fuel cells. In addition, we compared a conventional PEM fuel cell with identical Fe-N/C cathode loading to the bipolar deposition case. After a 15 hour test run the PEMFC cell showed a strongly increased overpotential at lower current densities, whereas the overpotential increase for the bipolar cell was only marginally in the same current density region. With this work we show a facile manufacturing approach that enables bipolar interface fuel cells with Fe-N/C catalysts, showing promising power densities at low total PGM-loadings.
CRIS-Team Scopus Importer:2020-05-22

Bipolar-Interface Hydrogen Fuel Cells: A Review and Perspective on Future High-Performance, Low Platinum-Group Metal Content Designs - Seeberger, Dominik; Hartert, Adrian; Mayerhöfer, Britta; Thiele, Simon (ChemElectroChem, 2021)
This Review elucidates the state-of-the-art, challenges, and future prospects for bipolar-interface-based fuel cells (BPIFCs), focusing on hydrogen-based systems. On the one side, it provides a summary of state-of-the-art design strategies for BPIFCs from different fields of application. On the other hand, it identifies the two most pivotal areas for a future understanding that particularly refer to the changed mass transport situations introduced by the bipolar fuel cell design, that is, the water management and the bipolar interface layer itself. All operation-relevant components such as the gas diffusion layers, catalyst layers, and membrane designs are discussed within the framework of these two main areas. As non-platinum-group metal (PGM) oxygen reduction is one of the key benefits of bipolar hydrogen fuel cells, a particular focus is put on this configuration. Several additional challenges that exclusively originate from non-PGM-based catalyst layers and possible mitigation approaches are discussed. One key insight is that these thick layers could take over the role of microporous layers in the future. Finally, we emphasize that there is a strong lack in both theoretical and experimental approaches that improve our understanding of the underlying processes in bipolar fuel cell designs.
CRIS-Team Scopus Importer:2021-03-26
Keywords: alkaline oxygen reduction reaction; bipolar membrane; Fe−N/C; hybrid fuel cells; PGM-free catalysts

Bipolar membrane electrode assemblies for water electrolysis - Thiele, Simon; Mayerhöfer, Britta; McLaughlin, David; Böhm, Thomas; Hegelheimer, Manuel; Seeberger, Dominik (ACS Applied Energy Materials, 2020)
We present the first analysis of a zero-gap bipolar membrane water electrolyzer fed with liquid water. Our electrolyzers feature a high-pH environment for the oxygen evolution reaction and a low-pH environment for the hydrogen evolution reaction. The advantages of proton exchange membrane water electrolysis can be combined with those of anion exchange membrane water electrolysis by including a water splitting bipolar interface. First, we develop a KOH-free anion exchange membrane electrolysis cell. The cell's alkaline anode serves as an integral building block on the path to a bipolar system. In a second step, we use this building block to investigate the cell operation characteristics of various cell configurations. We study the cell performance as the bipolar interface is shifted progressively toward the anode. A bipolar membrane with and without a water splitting catalyst resulted in cell current densities of 450 and 5 mA cm−2 at cell voltages of 2.2 V, respectively. Upon moving the bipolar interface directly between the acidic membrane and the high-pH anode, we achieved current densities of 9000 mA cm−2 at cell voltages of 2.2 V. Our study demonstrates the potential of this water electrolysis configuration, which should be adopted for further scientific studies and may show promise for future commercial water electrolysis systems.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Additive manufacturing; Aemion; Anion exchange membrane; Bipolar membrane; PH gradient; Water electrolysis; Water splitting

Carbon supported NiRu nanoparticles as effective hydrogen evolution catalysts for anion exchange membrane water electrolyzers - Ruck, Stephan; Körner, Andreas; Hutzler, A.; Bierling, Markus; Gonzalez, J.; Qu, W.; Bock, C.; Thiele, Simon; Peach, R.; Pham, C. (JPhys Energy, 2022)
Establishing anion exchange membrane water electrolysis (AEMWE) as a new technology for efficient hydrogen production requires cost-effective and high-performance catalyst materials. Here, we report the synthesis and comprehensive characterization of carbon supported NiRu alloy nanoparticles as a cost-effective hydrogen evolution reaction catalyst for AEMWEs. Different NiRu catalysts were synthesized using a facile and scalable impregnation method. Half-cell results showed the 'NiRu' catalyst with ca. 10 wt.% Ru to exhibit an increased noble metal mass activity and slightly decreased Tafel slope compared to a commercial Pt/C catalyst with 60 wt.% Pt. Further, we report the application of NiRu/C as a cathodic catalyst in AEMWE full cell for the first time. In full cell tests, the synthesized catalysts exhibit 2 A cm(-2) at 1.95 V with a low loading of 0.1 mg(PGM) cm(-2) at the cathode.
CRIS-Team WoS Importer:2022-10-28

Cerium Oxide Decorated Polymer Nanofibers as Effective Membrane Reinforcement for Durable, High-Performance Fuel Cells - Breitwieser, Matthias; Klose, Carolin; Hartmann, Armin; Buechler, Andreas; Klingele, Matthias; Vierrath, Severin; Zengerle, Roland; Thiele, Simon (Advanced Energy Materials, 2017)
High-power, durable composite fuel cell membranes are fabricated here by direct membrane deposition (DMD). Poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) nanofibers, decorated with CeO2 nanoparticles are directly electrospun onto gas diffusion electrodes. The nanofiber mesh is impregnated by inkjet-printed Nafion ionomer dispersion. This results in 12 µm thin multicomponent composite membranes. The nanofibers provide membrane reinforcement, whereas the attached CeO2 nanoparticles promote improved chemical membrane durability due to their radical scavenging properties. In a 100 h accelerated stress test under hot and dry conditions, the reinforced DMD fuel cell shows a more than three times lower voltage decay rate (0.39 mV h−1) compared to a comparably thin Gore membrane (1.36 mV h−1). The maximum power density of the DMD fuel cell drops by 9%, compared to 54% measured for the reference. Impedance spectroscopy reveals that ionic and mass transport resistance of the DMD fuel cell are unaffected by the accelerated stress test. This is in contrast to the reference, where a 90% increase of the mass transport resistance is measured. Energy dispersive X-ray spectroscopy reveals that no significant migration of cerium into the catalyst layers occurs during degradation. This proves that the PVDF-HFP backbone provides strong anchoring of CeO2 in the membrane.
CRIS-Team Scopus Importer:2023-03-29
Keywords: accelerated stress test; cerium oxide; direct membrane deposition; Gore; membrane degradation; polymer electrolyte membrane fuel cells

Communication-Proving the Importance of Pt-Interlayer Position in PEMWE Membranes for the Effective Reduction of the Anodic Hydrogen Content - Martin, Agate; Abbas, Dunia; Trinke, Patrick; Boehm, Thomas; Bierling, Markus; Bensmann, Boris; Thiele, Simon; Hanke-Rauschenbach, Richard (Journal of The Electrochemical Society, 2021)
Gas crossover through the membrane poses a significant challenge to proton exchange membrane water electrolysers. This work investigates the influence of the position of platinum-based recombination interlayers integrated in the membrane on the anodic hydrogen in oxygen content. The results show that all interlayer positions reduce the anodic hydrogen content without performance losses compared to the reference without interlayer. However, an interlayer positioned closer to the anode is more effective than closer to the cathode. Further, the effect of the interlayer is more pronounced with increasing anode pressure.
CRIS-Team WoS Importer:2021-10-08

Comprehensive investigation of novel pore-graded gas diffusion layers for high-performance and cost-effective proton exchange membrane electrolyzers - Lettenmeier, P.; Kolb, S.; Sata, N.; Fallisch, Arne; Zielke, L.; Thiele, Simon; Gago, A. S.; Friedrich, K. A. (Energy and Environmental Science, 2017)
Hydrogen produced by water electrolysis is a promising storage medium for renewable energy. Reducing the capital cost of proton exchange membrane (PEM) electrolyzers without losing efficiency is one of its most pressing challenges. Gas diffusion layers (GDL), such as felts, foams, meshes and sintered plates, are key stack components, but these are either inefficient or expensive. This study presents a new type of GDL produced via vacuum plasma spraying (VPS), which offers a large potential for cost reduction. With this technology, it is possible to introduce a gradient in the pore-size distribution along the thickness of the GDL by varying the plasma parameters and titanium powder particle sizes. This feature was confirmed by cross-section scanning electron microscopy (SEM). X-ray computed tomography (CT) and mercury intrusion porosimetry allowed determining the porosity, pore radii distribution, and pore entry distribution. Pore radii of ca. 10 μm could be achieved in the layers of the GDL close to the bipolar plate, while those in contact with the electrodes were in the range of 5 μm. The thermally sprayed Ti-GDLs allowed achieving PEM electrolyzer performances comparable to those of the state-of-the-art sintered plates and far superior than those of meshes. Moreover, a numerical model showed that the reduced capillary pressure and tortuosity eliminates mass transport limitations at 2 A cm-2. The results presented herein demonstrate a promising solution to reduce the cost of one of the most expensive components of the stack.
CRIS-Team Scopus Importer:2023-03-29

Correlating catalyst ink design and catalyst layer fabrication with electrochemical CO2 reduction performance - Liu, Guangxin; McLaughlin, David; Thiele, Simon; Van Pham, Chuyen (Chemical Engineering Journal, 2023)
The controllable fabrication of catalyst layers (CL) by tuning the multiscale structure formation is complex but vital to achieving optimum carbon dioxide reduction (CO2R) performance. An in-depth understanding on the role of each catalyst ink component and how multi-component interactions affect ink status, catalyst layer structure, and CO2R performance is crucial. In this work, the roles of different ingredients of catalyst ink were systematically investigated from simple binary inks to complete catalyst inks. Silver (Ag) particles-Nafion interactions were found to play a decisive role in stabilizing catalyst ink, mitigating agglomeration and particle sintering. The catalyst ink was comprehensively characterized and reported by static multiple light scattering (SMLS) for the first time in this paper. The evolution of catalyst ink was identified in three stages: stable, flocculation and sedimentation. Isopropanol (IPA)-rich solvents were found to be more effective in stabilizing catalyst ink due to better dispersed Nafion aggregates and further enhanced Ag particle-Nafion interactions. Subsequently, catalyst layer structure and CO2R performance were correlated with multi-component interactions in catalyst ink. Strong Ag particle-Nafion interactions were proven to promote not only ink stability, but also catalyst layer homogeneity and reaction site distribution. The carbon monoxide (CO) selectivity was boosted from 80.5 % to 94 % at an industrial meaningful current density of 200 mA/cm2 using commercial Ag nanoparticles by rational design of ink formulation, dispersing and fabrication processes. Simultaneously, a scalable manufacturing methodology of robust gas diffusion electrodes (GDEs) to achieve optimal CO2R performance was developed and validated.
CRIS-Team Scopus Importer:2023-02-24
Keywords: Catalyst ink; Catalyst layer fabrication; CO; Gas diffusion electrode; Static multiple light scattering

Critical Advances in Ambient Air Operation of Nonaqueous Rechargeable Li–Air Batteries - Liu, Lili; Guo, Haipeng; Fu, Lijun; Chou, Shulei; Thiele, Simon; Wu, Yuping; Wang, Jiazhao (Small, 2021)
Over the past few years, great attention has been given to nonaqueous lithium–air batteries owing to their ultrahigh theoretical energy density when compared with other energy storage systems. Most of the research interest, however, is dedicated to batteries operating in pure or dry oxygen atmospheres, while Li–air batteries that operate in ambient air still face big challenges. The biggest challenges are H2O and CO2 that exist in ambient air, which can not only form byproducts with discharge products (Li2O2), but also react with the electrolyte and the Li anode. To this end, recent progress in understanding the chemical and electrochemical reactions of Li–air batteries in ambient air is critical for the development and application of true Li–air batteries. Oxygen-selective membranes, multifunctional catalysts, and electrolyte alternatives for ambient air operational Li–air batteries are presented and discussed comprehensively. In addition, separator modification and Li anode protection are covered. Furthermore, the challenges and directions for the future development of Li–air batteries are presented.
CRIS-Team Scopus Importer:2023-03-29
Keywords: ambient air; electrolytes; Li anodes; Li–air batteries; oxygen-selective membranes

Cross-linked proton-exchange membranes with strongly reduced fuel crossover and increased chemical stability for direct-isopropanol fuel cells - Auffarth, Sebastian; Dafinger, Willibald; Mehler, Julia; Ardizzon, Valeria; Preuster, Patrick; Wasserscheid, Peter; Thiele, Simon; Kerres, Jochen (Journal of Materials Chemistry A, 2022)
Isopropanol fuel cells offer an attractive way to provide electric energy from a liquid, easily transportable fuel without producing significant amounts of CO2. The oxidation product acetone can be easily hydrogenated back to isopropanol to close the storage cycle, thereby avoiding the sophisticated handling of fugitive molecular hydrogen. Until now, direct-isopropanol fuel cells (DIFC) usually rely on various perfluorosulfonic acid ionomers, like Nafion, which are costly and have an unfavorable high fluorine content. Additionally, the dissolution of Nafion in isopropanol/acetone/water solutions within respective applications has prevented the long time operation of DIFCs so far. The swelling of those ionomers during operation promotes fuel crossover and reduces the system's overall energy efficiency. This study uses ionic cross-linking of polymer blends to manufacture chemically stable membranes and introduces a new click-like covalent cross-linking strategy for ion exchange polymers. Compared to Nafion XL, the manufactured membranes increase the maximum power density by up to 10%, resist a dissolution stress test up to 84 w% and reduce the detected isopropanol/acetone crossover up to 75/100% during fuel cell operation. Consequently, the material can be considered a major step toward the technical implementation of isopropanol fuel cell technologies.
CRIS-Team WoS Importer:2022-08-19

Digital Twin of a Hierarchical CO2 Electrolyzer Gas Diffusion Electrode - Mclaughlin, David; Bierling, Markus; Mayerhöfer, Britta; Schmid, Guenter; Thiele, Simon (Advanced Functional Materials, 2022)
The electrochemical reduction of CO2 provides a pathway to a sustainable carbon cycle, allowing for the production of hydrocarbons critical for both chemical industry and mobility. Major engineering challenges need to be met in order to achieve efficient and large-scale CO2 electrolysis. One central challenge is to find the optimum structure for the gas diffusion electrode at the heart of the electrolyzer. An optimum structure will achieve higher conversion efficiencies, lifetime, and product selectivity at lower cost. Critical structural properties of the electrode span the scale from nanometers to millimeters. To rationalize the optimization process, it behooves us to obtain a fully resolved multi-scale model of the electrode. This digital twin, produced by bridging scale and employing multiple imaging methods, enables the digital study, simulation, and modification of the structure of the electrode. The model is used to simulate the transport processes vital to the functioning of the electrode thus further advancing the digital twin. Subsequently, it is explored how changes to the structure affect the predicted transport properties. The digital twin presented is only supposed to be the kernel and will be complemented by numerous future works.
CRIS-Team WoS Importer:2023-01-20

Directly coated membrane electrode assemblies for proton exchange membrane water electrolysis - Holzapfel, Peter; Bühler, Melanie; Van Pham, Chuyen; Hegge, Friedemann; Böhm, Thomas; McLaughlin, David; Breitwieser, Matthias; Thiele, Simon (Electrochemistry Communications, 2020)
We present a novel membrane electrode assembly (MEA) fabrication method for proton exchange membrane water electrolysis (PEMWE). Inspired by previous work on PEM fuel cells (PEMFCs), we fabricated PEMWE-MEAs via direct membrane deposition (DMD). DMD-MEAs were fabricated by spray coating the membrane directly onto the cathode electrode – in this case, a carbon cloth substrate with microporous layer coated with Pt/C. The complete DMD-MEAs consisted of the membrane-cathode compound assembled with an anode electrode, which is a porous titanium fiber substrate coated with IrO2. Polarization experiments of DMD-MEAs show promising results: In comparison to a reference catalyst coated membrane (CCM) and a porous transport electrode (PTE) type MEA using a freestanding Nafion 117 membrane, we found very good electrochemical performances for DMD-MEAs. DMD-MEAs show slightly higher activation losses than the reference CCM. However, DMD-MEAs seem to exhibit reduced ohmic and mass transport losses compared to those manufactured using the CCM approach. Compared to the PTE-type reference DMD shows improvements for all three loss mechanisms. Similar as for PEMFCs, DMD may allow for a simplified fabrication route and higher degree of design freedom in PEMWE-MEA manufacturing due to the simple layer by layer fabrication approach.
CRIS-Team Scopus Importer:2019-12-27
Keywords: Direct membrane deposition; PEM water electrolysis; Porous transport electrodes

Direct membrane deposition - A fast and simple technique for membrane electrode assembly manufacturing - Klingele, M.; Vierrath, S.; Breitwieser, M.; Klose, C.; Thiele, Simon (ECS Transactions, 2017)
Thin yet strong membranes for polymer electrolyte fuel cells are currently widely researched because they combine low ionic resistance with satisfying fuel cell life-times. In this transaction we review our latest efforts in this direction, and present a fast and simple method for manufacturing chemically and mechanically reinforced polymer electrolyte membranes with thicknesses as low as 12 μm.
CRIS-Team Scopus Importer:2023-03-29

Dissolution of WO3 modified with IrOx overlayers during photoelectrochemical water splitting - Jenewein, Ken; Knöppel, Julius; Hofer, André; Kormanyos, Attila; Mayerhöfer, Britta; Speck, Florian; Bierling, Markus; Thiele, Simon; Bachmann, Julien; Cherevko, Serhiy (SusMat, 2023)
WO3, an abundant transition metal semiconductor, is one of the most discussed materials to be used as a photoanode in photoelectrochemical water-splitting devices. The photoelectrochemical properties, such as photoactivity and selectivity of WO3 in different electrolytes, are already well understood. However, the understanding of stability, one of the most important properties for utilization in a commercial device, is still in the early stages. In this work, a photoelectrochemical scanning flow cell coupled to an inductively coupled plasma mass spectrometer is applied to determine the influence of co-catalyst overlayers on photoanode stability. Spray-coated WO3 photoanodes are used as a model system. Iridium is applied to the electrodes by atomic layer deposition in controlled layer thickness, as determined by ellipsometry and x-ray photoelectron spectroscopy. Photoactivity of the iridium-modified WO3 photoanodes decreases with increasing iridium layer thickness. Partial blocking of the WO3 surface by iridium is proposed as the main cause of the decreased photoelectrochemical performance. On the other hand, the stability of WO3 is notably increased even in the presence of the thinnest investigated iridium overlayer. Based on our findings, we provide a set of strategies to synthesize nanocomposite photoelectrodes simultaneously possessing high photoelectrochemical activity and photostability.<br

Doped, Defect-Enriched Carbon Nanotubes as an Efficient Oxygen Reduction Catalyst for Anion Exchange Membrane Fuel Cells - Chuyen Van Pham; Britton, Benjamin; Boehm, Thomas; Holdcroft, Steven; Thiele, Simon (Advanced Materials Interfaces, 2018)
Bond polarization of doped atoms and carbon and lattice defects are considered important aspects in the catalytic mechanisms of oxygen reduction reaction (ORR) on heteroatom-doped carbon catalysts. Previous work on metal-free catalysts has focused either on bond polarization or lattice defects. Here multi-heteroatom doped defect-enriched carbon nanotubes (MH-DCNTs) that combine both effects to enhance ORR activity are designed. Lattice defects in MH-DCNTs are enriched by unzipping and length-shortening of carbon nanotubes, and also by creating carbon vacancies via decomposition of doped F atoms. Electrochemical analysis using rotating disc electrode voltammetry shows that the ORR kinetic current density of MH-DCNT increases with lattice-defect density, the latter of which is verified by Raman spectroscopy, while the onset potential increases with annealing temperatures. An optimized MH-DCNT ORR catalyst exhibits a half-wave potential of 0.81 V versus reversible hydrogen electrode and limiting current density of 5.0 mA cm−2 at an electrode rotation speed of 1600 rpm in 0.1 m KOH. Further, it is demonstrated that MH-DCNT, as a cathode catalyst layer in an anion exchange membrane fuel cell (AEMFC), delivers a peak power density of 250 mW cm−2, which is ≈70% the performance of an AEMFC using a conventional Pt/C catalyst.
CRIS-Team Scopus Importer:2023-03-29
Keywords: anion exchange polymer electrolyte; fuel cells; heteroatom doped carbon nanotubes; metal free catalyst; oxygen reduction reaction

Effect of Recombination Catalyst Loading in PEMWE Membranes on Anodic Hydrogen Content Reduction - Abbas, Dunia; Martin, Agate; Trinke, Patrick; Bierling, Markus; Bensmann, Boris; Thiele, Simon; Hanke-Rauschenbach, Richard; Boehm, Thomas (Journal of The Electrochemical Society, 2022)
Integrating platinum-based recombination catalysts into proton exchange membrane water electrolysis systems effectively reduces the anodic hydrogen content. We studied the effect of the platinum loading of an interlayer close to the anode within the membrane on the anodic hydrogen in oxygen content. For the investigated Pt-loadings between 1 mu g(Pt) cm(-2) and 140 mu g(Pt) cm(-2), the results revealed that for a 110 mu m membrane, 7 mu g(Pt) cm(-2) were sufficient to allow a safe operation at cathode pressures up to 10 bar. A further increase of the Pt-loading did not significantly improve the reduction of the anodic hydrogen in oxygen content.
CRIS-Team WoS Importer:2023-02-24

Electrochemical- and mechanical stability of catalyst layers in anion exchange membrane water electrolysis - Mayerhöfer, Britta; Speck, Florian D.; Hegelheimer, Manuel; Bierling, Markus; Abbas, Dunia; McLaughlin, David; Cherevko, Serhiy; Thiele, Simon; Peach, Retha (International Journal of Hydrogen Energy, 2022)
Anion exchange membrane (AEM) water electrolysis is considered a promising solution to future cost reduction of electrochemically produced hydrogen. We present an AEM water electrolyzer with CuCoOx as the anode catalyst and Aemion as membrane and electrode binder. Full cell experiments in pure water and 0.1 M KOH revealed that the optimum binder content depended on the type of electrolyte employed. Online dissolution measurements suggested that Aemion alone was not sufficient to establish an alkaline environment for thermodynamically stabilizing the synthesized CuCoOx in a neutral electrolyte feed. A feed of base is thus indispensable to ensure the thermodynamic stability of such non-noble catalyst materials. Particle loss and delamination of the catalyst layer during MEA operation could be reduced by employing a heat treatment step after electrode fabrication. This work summarizes possible degradation pathways for low-cost anodes in AEMWE, and mitigation strategies for enhanced system durability and performance.
CRIS-Team Scopus Importer:2022-01-21
Keywords: Aemion; Anion exchange membrane; Membrane electrode assembly; PGM-Free anode; Stability; Water electrolysis

Electrospun phosphonated poly(pentafluorostyrene) nanofibers as a reinforcement of Nafion membranes for fuel cell application - Mu'min, Muhammad Solihul; Komma, Miriam; Abbas, Dunia; Wagner, Maximilian; Krieger, Anja; Thiele, Simon; Böhm, Thomas; Kerres, Jochen (Journal of Membrane Science, 2023)
Nafion is a well-known perfluorosulfonic acid membrane widely used in fuel cells. However, despite its excellent properties, Nafion has limitations, including high hydrogen crossover. Reducing the hydrogen crossover is crucial since the H2 permeating through the membrane can directly react with O2 and produce radicals that can degrade Nafion. The hydrogen crossover can be minimized by increasing membrane thickness or by embedding nanostructures into Nafion. In this work, we report Nafion membranes reinforced by electrospun fibers made from phosphonated polypentafluorostyrene (PWN70) and, for comparison, unmodified polypentafluorostyrene (PPFSt). Composite membranes were obtained by spray-coating of Nafion onto the nanofiber meshes to fill the voids. From tensile tests, we found that PWN70/Nafion and PPFSt/Nafion composite membranes show higher Young's modulus and higher yield stress than pure Nafion. Fuel cell tests showed that PPFSt/Nafion composite membranes suffer from performance losses with increasing fiber loading, whereas PWN70/Nafion composite membranes perform similarly with non-reinforced Nafion. Furthermore, the use of PWN70/Nafion resulted in an H2 crossover reduction by 37–40% for atmospheric pressure, while it was not improved when using PPFSt/Nafion composite membranes. These results show the advantages of PWN70 nanofibers as a reinforcement for Nafion, which reduce the hydrogen crossover without sacrificing proton conductivity.
CRIS-Team Scopus Importer:2023-07-28
Keywords: Electrospinning; Fiber-reinforced composite membrane; Fuel cell; Hydrogen crossover; Phosphonated polypentafluorostyrene

Electrospun sulfonated poly(ether ketone) nanofibers as proton conductive reinforcement for durable Nafion composite membranes - Klose, Carolin; Breitwieser, Matthias; Vierrath, Severin; Klingele, Matthias; Cho, Hyeongrae; Buchler, Andreas; Kerres, Jochen; Thiele, Simon (Journal of Power Sources, 2017)
We show that the combination of direct membrane deposition with proton conductive nanofiber reinforcement yields highly durable and high power density fuel cells. Sulfonated poly(ether ketone) (SPEK) was directly electrospun onto gas diffusion electrodes and then filled with Nafion by inkjet-printing resulting in a 12 μm thin membrane. The ionic membrane resistance (30 mΩ*cm2) was well below that of a directly deposited membrane reinforced with chemically inert (PVDF-HFP) nanofibers (47 mΩ*cm2) of comparable thickness. The power density of the fuel cell with SPEK reinforced membrane (2.04 W/cm2) is 30% higher than that of the PVDF-HFP reinforced reference sample (1.57 W/cm2). During humidity cycling and open circuit voltage (OCV) hold, the SPEK reinforced Nafion membrane showed no measurable degradation in terms of H2 crossover current density, thus fulfilling the target of 2 mA/cm2 of the DOE after degradation. The chemical accelerated stress test (100 h OCV hold at 90 °C, 30% RH, H2/air, 50/50 kPa) revealed a degradation rate of about 0.8 mV/h for the fuel cell with SPEK reinforced membrane, compared to 1.0 mV/h for the PVDF-HFP reinforced membrane.
CRIS-Team Scopus Importer:2023-03-29
Keywords: Composite membrane; Direct membrane deposition; Electrospinning; Fiber reinforcement; PEMFC

Emerging Investigators in Electrochemical Energy Conversion and Storage 2018 - Love, Corey T.; Das, Prodip K.; Thiele, Simon; Mukherjee, Partha P.; Chen, Ruiyong; Jain, Ankur; Nelson, George J.; Banerjee, Soumik; Arava, Leela; Hatzell, Marta C.; Bazylak, Aimy; Brinkman, Kyle S.; et al. (Journal of Electrochemical Energy Conversion and Storage, 2018)
CRIS-Team Scopus Importer:2023-03-29

Energetics of Technical Integration of 2-Propanol Fuel Cells: Thermodynamic and Current and Future Technical Feasibility - Braun, Katharina; Wolf, Moritz; de Oliveira, Ana; Preuster, Patrick; Wasserscheid, Peter; Thiele, Simon; Weiß, Lukas; Wensing, Michael (Energy Technology, 2022)
2-Propanol/acetone is a promising liquid organic hydrogen carrier system for fuel cell reactions. Herein, six different concepts for a 2-propanol/acetone fuel cell system are evaluated in MATLAB simulation with respect to their thermodynamic integration and technical feasibility. Four of the concepts use a direct 2-propanol fuel cell while the other two first release molecular hydrogen from 2-propanol and subsequently use a hydrogen fuel cell. The presented liquid phase 2-propanol fuel cell concept is thermodynamically feasible but cannot be realized technically using commercial Nafion membranes, due to membrane dissolution by the 2-propanol/acetone/water fuel mixture. Gaseous 2-propanol fuel cells imply a high heating requirement for the evaporation of the fuel. A direct high-temperature fuel cell using 2-propanol is thermodynamically feasible because there is less water in the overall system but is not technically feasible because of the esterification of phosphoric acid. A very interesting option is the conversion of gaseous 2-propanol to pressurized hydrogen in an electrochemical pumping step followed by a hydrogen fuel cell, because here the waste heat of a sufficiently hot hydrogen fuel cell can drive the 2-propanol evaporation.
CRIS-Team Scopus Importer:2022-07-15
Keywords: 2-propanol fuel cell system; balance of plant; energy balancing; system integration; technical integration

Essentials of High Performance Water Electrolyzers - From Catalyst Layer Materials to Electrode Engineering - Pham, Chuyen Van; Escalera-Lopez, Daniel; Mayrhofer, Karl; Cherevko, Serhiy; Thiele, Simon (Advanced Energy Materials, 2021)
Proton-exchange membrane water electrolyzers (PEMWEs) will play a key role in future sustainable hydrogen production for mobility, households or chemical industry. Yet, the anode in PEMWEs, where the pivotal oxygen evolution reaction takes place, needs further improvement in terms of performance and cost. Both catalyst materials and electrode structure have to be optimized in order to inhibit degradation and reduce noble metal loadings. This review focuses on a holistic approach, covering all catalyst material, electrode structure, and transport layers within the framework of an overall electrode design, which not only optimizes the catalyst but also, all components of the electrode in conjunction. This review defines the goals for performance metrics of future PEMWEs in terms of power density and durability of the anode. Moreover, it summarizes manufacturing techniques and approaches that have a chance to be upscaled to meet the megawatt deployment of PEMWEs. The different aspects described jointly in this review such as novel catalyst system with higher intrinsic and structural performance or graded porous transport layers shall help to advance a next generation of electrodes.
CRIS-Team WoS Importer:2021-10-29

Evaluating Electrocatalysts at Relevant Currents in a Half-Cell: The Impact of Pt Loading on Oxygen Reduction Reaction - Ehelebe, Konrad; Seeberger, Dominik; Paul, Mike T. Y.; Thiele, Simon; Mayrhofer, Karl; Cherevko, Serhiy (Journal of The Electrochemical Society, 2019)
In this work gas diffusion electrode (GDE) half-cells experiments are proposed as powerful tool in fuel cell catalyst layer evaluation as it is possible to transfer the advantages of fundamental methods like thin-film rotating disk electrode (TF-RDE) such as good comparability of results, dedicated elimination of undesired parameters etc. to relevant potential ranges for fuel cell applications without mass transport limitations. With the developed setup and electrochemical protocol, first experiments on different Pt/C loadings confirm excellent reproducibility. Thereby mass-specific current densities up to 30 A mg(Pt)(-1) at 0.6 V vs. RHE are achieved. From a methodological perspective, good comparability to single cell measurements is obtained after theoretical corrections for temperature and concentration effects. In comparison to previous studies with GDE half-cells, polarization curves without severe mass transport limitations are recorded in a broad potential window. All these achievements indicate that the proposed method can be an efficient tool to bridge the gap between TF-RDE and single cell experiments by providing fast and dedicated insights into the effects of catalyst layers on oxygen reduction reaction performance. This method will enable straightforward and efficient optimization of catalyst layer composition and structure, especially for novel catalysts, thereby contributing to the performance enhancements of fuel cells with reduced Pt loading. (c) The Author(s) 2019. Published by ECS. This is an open access article distributed under the terms of the Creative Commons Attribution 4.0 License (CC BY, http://creativecommons.org/licenses/by/4.0/), which permits unrestricted reuse of the work in any medium, provided the original work is properly cited. [DOI: 10.1149/2.0911915jes]
CRIS-Team WoS Importer:2019-12-13

Evaluation of the Efficiency of an Elevated Temperature Proton Exchange Membrane Water Electrolysis System - Bonanno, Marco; Mueller, Karsten; Bensmann, Boris; Hanke-Rauschenbach, Richard; Peach, Retha; Thiele, Simon (Journal of The Electrochemical Society, 2021)
In recent years, a significant interest has been growing in elevated temperature (ET) electrolytes for proton exchange membrane water electrolysis (PEMWE). In this study, the energy and exergy analysis developed for PEMWE has been extended to evaluate the performance of ET-PEMWE, with the model aiming to utilise the energy in the most efficient manner and also take into account potential heat losses. The latter is particularly important considering that heat losses become more pronounced with higher temperature differences. The model shows that the stack operates in autothermic mode over a considerable range of current density. Thus heating inputs to the stack and feed water become progressively unnecessary as polarization losses make up for these heating requirements. This also allows surplus heat to be utilised for secondary applications. The exergy efficiency for ET has been calculated to surpass that for low temperature (LT), with the maximum improvement reaching 3.8% points. Taking into account exergy favours higher temperature differences-a benefit which outweighs the fact that a greater quantity of thermal power is recovered in the LT system (due to higher polarization losses). This finding also shows the suitability of adopting exergy efficiency as the performance indicator for PEMWE systems.
CRIS-Team WoS Importer:2021-10-01

Evaluations of Concepts for the Integration of Fuel Cells in Liquid Organic Hydrogen Carrier Systems - Müller, Karsten; Thiele, Simon; Wasserscheid, Peter (Energy & Fuels, 2019)
Liquid organic hydrogen carrier (LOHC) systems store hydrogen through covalent bonds. As the release of H2 from the LOHC carrier is an endothermic process, clever heat and system integration of this critical step with the exothermic fuel cell operation is highly desirable. The aim of this study is the evaluation of different configurations of this sequence. The results allow decisions on efficient process options. With respect to energy efficiency, the worst case is electric heating for providing the LOHC dehydrogenation heat. Most favorable, in contrast, is full heat integration between a high-temperature fuel cell and the dehydrogenation unit. Partial combustion of hydrogen for heat provision represents an attractive choice. Alternatively, hydrogen transfer to a CO2-free, organic fuel cell is another interesting option. This includes transfer hydrogenation, for example, conversion of acetone to isopropanol, followed by direct conversion of the latter in a fuel cell. While hydrogen combustion-driven dehydrogenation promises high overall power densities, the hydrogen transfer to an organic fuel represents a very efficient technology.
CRIS-Team Scopus Importer:2019-10-15

Fabrication of a Robust PEM Water Electrolyzer Based on Non-Noble Metal Cathode Catalyst: [Mo3S13]2− Clusters Anchored to N-Doped Carbon Nanotubes - Holzapfel, Peter K. R.; Buehler, Melanie; Escalera-Lopez, Daniel; Bierling, Markus; Speck, Florian; Mayrhofer, Karl; Cherevko, Serhiy; Pham, Chuyen V.; Thiele, Simon (Small, 2020)
High investment costs and a dependence on noble metal catalysts currently obstruct the large-scale implementation of proton exchange membrane water electrolyzers (PEMWEs) for converting fluctuating green electricity into chemical energy via water splitting. In this context, this work presents a high-performing and stable non-noble metal catalyst for the hydrogen evolution reaction (HER), consisting of [Mo3S13]2− clusters supported on nitrogen doped carbon nanotubes (NCNTs). Strikingly, a significant electrochemically induced activation of the Mo3S13-NCNT catalyst at high current densities is observed in full cell configuration, enabling a remarkable current density of 4 A cm−2 at a cell voltage of 2.36 V. To the authors’ knowledge, this is the highest reported value to date for a PEMWE full cell using a non-noble metal HER catalyst. Furthermore, only a minor degradation of 83 µV h−1 is observed during a stability test of 100 h constant current at 1 A cm−2, with a nearly unchanged polarization behavior after the current hold. Catalyst stability and activity are additionally analyzed via online dissolution measurements. X-ray photoelectron spectroscopy examination of the catalyst before and after electrochemical application reveals a correlation between the electrochemical activation occurring via electrodissolution with changes in the molecular structure of the Mo3S13-NCNT catalyst.
CRIS-Team Scopus Importer:2020-09-04
Keywords: hydrogen evolution reaction; molybdenum sulfide; non-noble metal catalysts; porous transport electrodes; proton exchange membrane water electrolysis

FIB/SEM tomography segmentation by optical flow estimation - Moroni, Riko; Thiele, Simon (Ultramicroscopy, 2020)
Focused ion beam/scanning electron microscopy tomography (FIB/SEM tomography) is the method of choice for the tomographic reconstruction of mesoporous materials systems in various fields such as batteries, fuel cells, filter applications or composite materials. However, due to so called shine-through artifacts in FIB/SEM tomographies of porous materials, their segmentation into pore space and solid material is a nontrivial task. Here, an optical flow-based method that utilizes shine-through artifacts for segmentation is introduced. Subsequently, the performance of the method is discussed by means of tomographic datasets of a polymer electrolyte fuel cell catalyst layer and a lithium ion battery composite electrode. Previous, manual segmentations of these datasets allow the evaluation of the results – for the catalyst layer an accuracy of 86.6% and a precision of 84.0% is reached. In both cases, the optical flow-based approach gives significantly better results than comparable segmentations obtained from gray-value threshold binarization.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Focused ion beam; Optical flow estimation; Porous materials systems; Scanning electron microscope; Segmentation; Tomography

From catalyst coated membranes to porous transport electrode based configurations in PEM water electrolyzers - Buehler, Melanie; Holzapfel, Peter; Mclaughlin, David; Thiele, Simon (Journal of The Electrochemical Society, 2019)
So far the superior cell polarization behavior of membrane electrode assemblies (MEAs) using catalyst coated membranes (CCMs) as compared to those using porous transport electrodes (PTEs) was a paradigm in proton exchange membrane water electrolyzers (PEMWEs). However, this paradigm was so far neither systematically investigated nor understood. In this study, we investigate the changes in PEMWE polarization behavior upon gradually changing the MEA from a full CCM toward a full PTE-type configuration. We explain all observed findings based on the idea for a structural model of discontinuous catalyst layers. Our results show, that for current densities above 750 mA cm−2, PTE-based MEAs can result in a better polarization behavior than CCMs. Therefore, the prevailing paradigm was disproved. CCMs showed better kinetics, while PTE-type configurations performed more reproducible than CCMs despite rougher surfaces. Due to the trend of a stabilizing HFR-free cell voltage, an improved mass transport behavior of the PTE-type configurations at high current densities is assumed. Within the error-tolerance, no clear differences between PTE and CCM-based configurations in ohmic resistance could be determined. We conclude that PTE-based configurations for PEMWE, as alternatives to standard CCM-configurations, could be highly important for future manufacturing techniques depending on the application’s needs.
CRIS-Team Scopus Importer:2019-10-15

Fuel cell catalyst layer evaluation using a gas diffusion electrode half-cell: Oxygen reduction reaction on Fe-N-C in alkaline media - Ehelebe, Konrad; Ashraf, Talal; Hager, Simon; Seeberger, Dominik; Thiele, Simon; Cherevko, Serhiy (Electrochemistry Communications, 2020)
Anion exchange membrane fuel cells (AEMFC) are a promising technology to allow the application of non-precious metal catalysts. While many of such catalysts have been identified in numerous recent fundamental research studies, reports evaluating these catalysts in realistic AEMFC catalyst layers together with stability assessments are rare. In the present work we show that fast and reliable evaluation and optimization of Fe-N-C-based oxygen reduction reaction (ORR) catalyst layers can be achieved using a gas diffusion electrode (GDE) half-cell approach. To set a benchmark in such measurements, a commercial Pajarito Powder Fe-N-C catalyst and commercial AemionTM ionomer are used. It is demonstrated that the ORR performance can be increased significantly by fine-tuning of the ionomer activation time. Furthermore, the optimized Fe-N-C-based catalyst layer shows very high stability with no observable performance deterioration after 5000 cycles in the 0.6–1.0 V vs. RHE potential window.
CRIS-Team Scopus Importer:2020-06-16
Keywords: Alkaline fuel cell; Alkaline ionomer; Fe-N-C; Gas diffusion electrode; Non-noble metal catalyst; Oxygen reduction reaction

H+-conducting aromatic multiblock copolymer and blend membranes and their application in pem electrolysis - Bender, Johannes; Mayerhöfer, Britta; Trinke, Patrick; Bensmann, Boris; Hanke-Rauschenbach, Richard; Krajinovic, Katica; Thiele, Simon; Kerres, Jochen (Polymers, 2021)
As an alternative to common perfluorosulfonic acid-based polyelectrolytes, we present the synthesis and characterization of proton exchange membranes based on two different concepts: (i) Covalently bound multiblock-co-ionomers with a nanophase-separated structure exhibit tunable properties depending on hydrophilic and hydrophobic components’ ratios. Here, the blocks were synthesized individually via step-growth polycondensation from either partially fluorinated or sulfonated aromatic monomers. (ii) Ionically crosslinked blend membranes of partially fluorinated polybenzimidazole and pyridine side-chain-modified polysulfones combine the hydrophilic component’s high proton conductivities with high mechanical stability established by the hydrophobic components. In addition to the polymer synthesis, membrane preparation, and thorough characterization of the obtained materials, hydrogen permeability is determined using linear sweep voltammetry. Furthermore, initial in situ tests in a PEM electrolysis cell show promising cell performance, which can be increased by optimizing electrodes with regard to binders for the respective membrane material.
CRIS-Team Scopus Importer:2021-10-29
Keywords: Acid–base blend membranes; Electrolyzer; Hydrogen crossover; MEA; Multiblock-co-ionomers; Partially fluorinated and sulfonated poly(arylene)s; PEM

High performance direct organic fuel cell using the acetone/isopropanol liquid organic hydrogen carrier system - Hauenstein, Pascal; Seeberger, Dominik; Wasserscheid, Peter; Thiele, Simon (Electrochemistry Communications, 2020)
Liquid Organic Hydrogen Carrier (LOHC) systems offer a very interesting option for hydrogen storage in the existing infrastructure for common fuels. Technically most attractive is the direct use of LOHC-bound hydrogen in a low-temperature PEM fuel cell. Here, the isopropanol/acetone LOHC system is suggested to produce electricity from a condensable liquid without CO2 emissions. A high-performance direct isopropanol fuel cell using a vaporizer and a commercial fuel cell test system is demonstrated. For the first time backpressure is used to enhance the performance. The self-fabricated GDEs combined with a Nafion composite membrane achieved a power density of 203 mW cm−2 for Isopropanol/Air operation at 300 kPa absolute and 85 °C. By increasing the operation temperature to 100 °C a peak power density of 254 mW cm−2 is achieved, exceeding the highest reported values for isopropanol fuel cells operated with air by over 80%. The observed increase in performance can be attributed to the higher reaction rate of the electrooxidation of isopropanol at the anode side during pressurized conditions and to the reduced acetone-poisoning of the Pt-Ru catalyst at elevated temperatures.
CRIS-Team Scopus Importer:2020-07-24
Keywords: Backpressure; Direct isopropanol fuel cells; LOHC; Organic fuel cells; Temperature

Hydrogen extraction from methane-hydrogen mixtures from the natural gas grid by means of electrochemical hydrogen separation and compression - Mrusek, Stephan; Blasius, Marco; Morgenroth, Frank; Thiele, Simon; Wasserscheid, Peter (International Journal of Hydrogen Energy, 2023)
One interesting option to store and transport hydrogen in the future is to blend it into the natural gas grid. In this paper, we present technological insights regarding electrochemical hydrogen separation and compression (EHC/S), a technology that enables extraction of compressed and purified hydrogen from such blends. Our contribution discusses two use cases, namely i) hydrogen separation to recover purified hydrogen under pressure, and ii) hydrogen removal to protect downstream methane consumers from excessive hydrogen levels. Our experimental work with a laboratory scale EHC/S centers on efficiency aspects. We show that at low hydrogen contents in dry feed gas, gas humidification causes relevant thermal energy consumption, that cannot be provided by EHC/S waste heat. We also show that hydrogen recovery is restricted by mass transport if the residence time in the EHC device is too short. Simultaneous hydrogen separation and compression from 5% hydrogen in methane is demonstrated yielding hydrogen at 6 bara at the cathode.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Electrochemical hydrogen compression; Electrochemical hydrogen separation; Hydrogen purification; Hydrogen storage; Natural gas grid

Impact of Carbon Support Corrosion on Performance Losses in Polymer Electrolyte Membrane Fuel Cells - Hegge, Friedemann; Sharman, Jonathan; Moroni, Riko; Thiele, Simon; Zengerle, Roland; Breitwieser, Matthias; Vierrath, Severin (Journal of The Electrochemical Society, 2019)
Corrosion of the carbon support leads to a severe decay in the performance of PEM fuel cells, mainly due to an increase in the oxygen transport resistance. To investigate the effect of degradation on oxygen transport, we cycled MEAs between 1-1.5 V and analyzed the electrode structure with FIB-SEM tomography at various ageing states. The tomography results show that the electrode structure changes over 1000 cycles in terms of thickness (7.8 to 6.5 mu m), porosity (44 to 38%) and diffusivity (9 to 8.10(5) m(2)s(-1)). Limiting current measurements in the wet (hydrogen/air) and dry state (hydrogen pumping) allowed the pressure dependent and pressure independent mass transport resistances to be distinguished and to quantify the impact of product water. The pressure independent resistance increased from 24 to 41 sm(-1). Considering the marginal contribution of the catalyst pore space resistance (3 to 4 sm(-1)) it is concluded that the largest portion of the increase (50%) is caused by an increased local mass transport resistance. This is due to a decrease of the electrode roughness factor (282 to 169). The limiting current under wet conditions shows that another 44% could stem from a change in the wetting behavior, while 6% remains unexplained. (C) The Author(s) 2019. Published by ECS.
CRIS-Team WoS Importer:2019-09-10

Impact of catalyst loading, ionomer content, and carbon support on the performance of direct isopropanol fuel cells - Hauenstein, Pascal; Mangoufis Giasin, Iosif; Seeberger, Dominik; Wasserscheid, Peter; Mayrhofer, Karl; Katsounaros, Ioannis; Thiele, Simon (Journal of Power Sources Advances, 2021)
Liquid Organic Hydrogen Carriers (LOHC) offer a promising solution for hydrogen storage in the existing infrastructure for conventional fuels. Within this framework, the isopropanol/acetone couple as a light-LOHC system is used to generate electricity in a direct isopropanol fuel cell (DIFC). This work focuses on the impact of catalyst loading, ionomer content and catalyst support on the performance of DIFCs. We achieve a performance rise from 95 mW cm-2 to 219 mW cm-2 under air operation by increasing the anode catalyst loading from 0.5 mg cm-2 to 4 mg cm-2, which can be attributed to the increased abundance of active catalyst sites with higher loadings. In contrast, we find that the cathode loading for the oxygen reduction reaction (ORR) plays a minor role in the performance of DIFCs. Therefore, the cathode loading can be minimized to decrease the total amount of platinum-group metals and, consequently, to save cost. It was also found that an ionomer content of 30% on the anode side is optimal. Additionally, different carbon supports were investigated, where advanced high surface area carbon support showed superior performance to Vulcan with an increase of 20% in power density, motivating the development of new carbon supports for DIFCs.
CRIS-Team Scopus Importer:2021-07-30
Keywords: 2-propanol fuel cell; Carbon support; Catalyst loading; Direct isopropanol fuel cells; Ionomer content; LOHC; Organic fuel cells

Improved Hydrogen Oxidation Reaction Activity and Stability of Buried Metal-Oxide Electrocatalyst Interfaces - Speck, Florian D.; Ali, Farhan S. M.; Paul, Michael T. Y.; Singh, Ramesh K.; Böhm, Thomas; Hofer, André; Kasian, Olga; Thiele, Simon; Bachmann, Julien; Dekel, Dario R.; Kallio, Tanja; Cherevko, Serhiy (Chemistry of Materials, 2020)
Various bifunctional metal-oxide composites have recently been proposed as advanced hydrogen oxidation reaction (HOR) electrocatalysts for anion-exchange membrane fuel cells (AEMFCs). It is postulated that metal and oxide are active sites for the adsorption of hydrogen/proton and hydroxide ions, respectively. Of particular interest are the so-called buried interfaces. To investigate processes governing activity and stability at such interfaces, we prepare model Pd and Pt electrocatalysts which are fully covered by thin CeOx films. We investigate how oxide thickness influences HOR activity and dissolution stability of the electrocatalysts. It is found that materials behave very differently and that only Pd exhibits an enhanced HOR activity, while both oxide-protected metals are more stable toward dissolution. A 10-fold decrease in dissolution and 15-fold increase in HOR exchange current density are demonstrated for the optimized Pd/CeOx composites in comparison to pure Pd. We assess the mechanism of the electrocatalytic improvement as well as the role of the protective oxide films in such systems through advanced electrochemical and physical analysis. It is highlighted that a uniform, semipermeable oxide layer with a maximized electrocatalyst-oxide interface is crucial to form HOR catalysts with improved activity and stability.
CRIS-Team WoS Importer:2020-10-23

Improving Hydrogen Release From Oxygen-Functionalized LOHC Molecules by Ru Addition to Pt/C Catalysts - Maurer, Lukas; Pham, Chuyen v.; Fritsch, Birk; Jeppesen, Henrik S.; Etter, Martin; Hutzler, Andreas; Neder, Reinhard; Wolf, Moritz; Auer, Franziska; Thiele, Simon; Wasserscheid, Peter (ChemCatChem, 2024)
Bimetallic PtRu/C catalysts have been prepared by depositing Ru onto a commercial Pt/C catalyst and subsequent thermal annealing. Different Pt : Ru ratios of 1 : 1, 2 : 1, 4 : 1, 8 : 1, and 16 : 1 have been investigated with annealing temperatures of 350 and 500 °C. Using X-ray diffraction (XRD), synchrotron powder X-ray diffraction (SPXRD) combined with pair distribution function (PDF) analysis and scanning transmission electron microscopy with energy dispersive X-ray spectrum imaging (STEM-EDXS), we show that diffusion of Ru into the fcc crystal structure of the Pt nanoparticles takes place during thermal annealing. Partial segregation and the formation of Pt nanoclusters on the bimetallic surface was observed depending on the Pt : Ru ratio. The annealing process does not only cause a high Pt dispersion but also affects the electronic structure of the Pt surface by broadening the d-band thus facilitating the product's desorption from the surface of the bimetallic particle. These beneficial effects have been exemplified for the catalytic dehydrogenation of dicyclohexylmethanol, a promising hydrogen carrier compound with 7.2 wt% hydrogen capacity. The most active catalyst material among the tested supported alloys and monometallic reference materials was Pt4Ru1/C after annealing at 500 °C, which increased the hydrogen release productivity by 65 % compared to the unmodified Pt/C catalyst.
CRIS-Team Scopus Importer:2024-07-19
Keywords: Alloys; Chemical hydrogen storage; Dehydrogenation; Heterogeneous catalysis; LOHC; Platinum; Ruthenium

In Search of Lost Iridium: Quantification of Anode Catalyst Layer Dissolution in Proton Exchange Membrane Water Electrolyzers - Milosevic, Maja; Böhm, Thomas; Körner, Andreas; Bierling, Markus; Winkelmann, Leonard; Ehelebe, Konrad; Hutzler, Andreas; Suermann, Michel; Thiele, Simon; Cherevko, Serhiy (ACS Energy Letters, 2023)
Understanding catalyst dissolution pathways in proton exchange membrane water electrolyzers is paramount for developing mitigation strategies aiming toward higher durability and lower catalyst loadings. To this end, Ir dissolution has been extensively studied using aqueous model systems but not in real devices. Aiming to bridge this knowledge gap, we use a metal-free water electrolysis setup to determine the mass balance of the dissolved Ir in an electrolyzer when applying a protocol mimicking intermittent operation. We find that the main Ir sinks are the cathode catalyst layer and the membrane, while Ir dissolution into the water lines is significantly lower. Although reproducible estimation of Ir present in the membrane is challenging, quantification of Ir within the cathode is reliable and efficient. This new finding implies that tracking Ir present in the cathode can be used to estimate anode catalyst stability, thus accelerating catalyst development and operational parameters optimization.
CRIS-Team Scopus Importer:2023-07-07

IrO2 coated TiO2 core-shell microparticles advance performance of low loading proton exchange membrane water electrolyzers - Pham, Chuyen Van; Bühler, Melanie; Knöppel, Julius; Bierling, Markus; Seeberger, Dominik; Escalera-López, Daniel; Mayrhofer, Karl; Cherevko, Serhiy; Thiele, Simon; Thiele, Simon (Applied Catalysis B-Environmental, 2020)
Herein we present novel IrO2 coated TiO2 core-shell microparticles (IrO2@TiO2) as an oxygen evolution reaction catalyst. We compare the IrO2@TiO2 catalyst to commercial TiO2 supported IrO2 catalyst (IrO2/TiO2) and pure IrO2 catalyst powder. A stability analysis via on-line inductively coupled plasma mass spectrometry based on the S-number, a descriptor considering both energy efficiency and catalyst utilization efficiency, shows that the IrO2@TiO2 catalyst shows high potential for practical applications. This was further confirmed by full-cell tests showing superior performance of the IrO2@TiO2 catalyst with moderate and low loadings of 1.2 mgIr cm−2 and 0.4 mgIr cm−2, respectively. The core-shell catalyst is synthesized via facile route suitable for large quantities. Moreover, stable inks from the synthesized catalyst powder make this system appealing for large scale manufacturing of cells. Given the facile synthesis route, high activity, and good stability, the IrO2@TiO2 catalyst is potentially suitable for industry proton exchange membrane water electrolysis application.
CRIS-Team Scopus Importer:2020-02-28
Keywords: Core shell catalyst; Iridium oxide catalyst; Oxygen evolution reaction; Proton exchange membrane; Water electrolysis

Isopropanol electro-oxidation on Pt-Ru-Ir: A journey from model thin-film libraries towards real electrocatalysts - Minichová, Mária; Van Pham, Chuyen; Xiao, Bin; Savan, Alan; Hutzler, Andreas; Körner, Andreas; Khalakhan, Ivan; Rodríguez, Miquel Gamón; Mangoufis-Giasin, Iosif; Briega-Martos, Valentín; Kormányos, Attila; Katsounaros, Ioannis; et al. (Electrochimica Acta, 2023)
Liquid fuels are considered a promising alternative to hydrogen in proton exchange membrane fuel cells. In particular, isopropanol, which can be selectively oxidised to acetone and further hydrogenated back to isopropanol using electrochemical and heterogeneous catalysis routes, respectively, opens the possibility of zero-emission fuel cell operation without complex management of molecular H2. However, the maximum electric power of such fuel cells is still relatively low, which is attributed to the poisoning of state-of-the-art Pt-Ru electrocatalysts by adsorbed acetone and/or Ru oxide/hydroxide. Here, in order to mitigate Pt-Ru poisoning at higher anodic potentials during isopropanol oxidation in acidic media, the effect of the addition of Ir, a less oxophilic element than Ru, on the activity and stability during dynamic experiments of Pt-Ru is systematically investigated. To identify the most active compositions, Pt-Ru-Ir thin-film material libraries are prepared using magnetron co-sputtering. The electrocatalytic activity of the libraries is screened using a high-throughput scanning flow cell setup. Catalysts with the highest activity are further synthesised in the form of carbon-supported nanoparticles. Comparing the two systems, similar trends are observed, highlighting the model material libraries being an excellent starting point for novel catalyst development. Besides electrocatalytic activity, catalyst shelf-life and dissolution stability are studied. While significant ageing in the air is found, partial reactivation is possible using a reductive treatment. The dissolution of the most promising nanoparticulate electrocatalyst is evaluated using online inductively coupled plasma mass spectrometry to assess the effect of Ir addition on Pt and Ru stability. No significant stabilising role of Ir, however, is observed. Hence, further optimisation of Pt-Ru or Pt-Ru-Ir is still needed to improve isopropanol fuel cell performance.
CRIS-Team Scopus Importer:2023-02-24
Keywords: Alcohol oxidation; Electrocatalysis; Fuel cell; ICP-MS; Stability

Local hydration in ionomer composite membranes determined with confocal Raman microscopy - Mu'min, Muhammad Solihul; Böhm, Thomas; Moroni, Riko; Zengerle, Roland; Thiele, Simon; Vierrath, Severin; Breitwieser, Matthias (Journal of Membrane Science, 2019)
Water management in electrochemical energy applications like fuel cells has a crucial impact on performance, in particular on the ionic conduction of ionomer membranes. To strengthen the understanding of water management in such devices, we report a novel method for non-destructive measurements of the hydration of composite membranes based on confocal Raman microscopy. Composite membranes were produced by spray-coating of Nafion into a mesh of electrospun poly(vinylidene fluoride-co-hexafluoropropylene)/polyvinylpyrrolidone (PVDF-HFP/PVP) blend nanofibers. Hydration levels of several pure nanofiber meshes and nanofiber/Nafion composites were evaluated by linear least squares fitting of reference Raman spectra to hyperspectral images. We found that spectral contribution of water to nanofiber spectra depends on the PVDF-HFP/PVP ratio and is independent from fiber diameter. Further, we were able to reliably determine nanofiber polymer composition of single fibers based on Raman spectroscopy. Raman imaging of composite membranes was performed at ambient air and fully hydrated conditions to study the local hydration in PVDF-HFP/PVP/Nafion composites as well as in a Nafion XL membrane. 2D through-plane mappings revealed that the nanofiber hydration positively correlated with PVP content. In the Nafion XL membrane, the polytetrafluoroethylene-based reinforcement was verified as a hydrophobic layer sandwiched between Nafion ionomer, which showed a more than 10% reduced hydration compared to the outer Nafion layers. These results motivate the use of confocal Raman microscopy as a novel method to investigate the local water distribution in ionomer composite membranes that are widely used in electrochemical energy conversion.
CRIS-Team Scopus Importer:2019-05-28
Keywords: Confocal Raman microscopy; Electrospun nanofibers; Hydration; Hydrophilicity; Membrane

Membrane interlayer with PT recombination particles for reduction of the anodic hydrogen content in PEM water electrolysis - Klose, Carolin; Trinke, Patrick; Boehm, T.; Bensmann, Boris; Vierrath, S.; Hanke-Rauschenbach, Richard; Thiele, Simon (Journal of The Electrochemical Society, 2018)
Polymer electrolyte membrane (PEM) water electrolysis is a key technology for sustainable hydrogen based energy supply. Gas permeation through the PEM leads to hydrogen in oxygen at the anode side posing a safety hazard and therefore restricting the operation window of PEM water electrolysis, especially when operating under pressure. In this work the hydrogen in oxygen content at the anode is significantly reduced when a recombination interlayer is integrated into the membrane electrode assemblies (MEAs) compared to reference MEAs without interlayer. The recombination interlayer with a platinum loading of 0.02 mg cm−2 is sprayed between two membranes that are coated with anode and cathode catalysts on the outside. The permeating H2 and O2 forms water at the recombination interlayer, leading to higher gas purity and resolving safety issues. In case of the MEAs with interlayer also a constant current hold at 1 A cm−2 for 245 h revealed only a slight increase of the hydrogen in oxygen content (below 140·10−6 vol.% h−1) whereas for the reference MEAs without interlayer a stronger increase was observed (above 1250·10−6 vol.% h−1). Furthermore, the long-term experiments showed no increased degradation rates compared to the reference MEAs.
CRIS-Team Scopus Importer:2023-03-29

[Mo3S13]2− Cluster Decorated Sulfur-doped Reduced Graphene Oxide as Noble Metal-Free Catalyst for Hydrogen Evolution Reaction in Polymer Electrolyte Membrane Electrolyzers - Pham, Chuyen; Zana, Alessandro; Arenz, Matthias; Thiele, Simon (ChemElectroChem, 2018)
Non-noble metal catalysts represent a central direction of seminal scientific research in electrocatalysis due to the high cost and scarcity of present Pt-based catalysts for the hydrogen evolution reaction (HER) in particular. Here, we develop a novel hybrid material of [Mo3S13]2− clusters decorated sulfur doped reduced graphene oxide (Mo3S13-SrGO) as a HER catalyst for water electrolyzers. Doped S elements act as anchor points for [Mo3S13]2− cluster attachment via forming doped S−Mo coordinate bonds, which increase stability of the hybrid catalyst as well as contribute additional active sites for the HER. SrGO supports substantially enhance the activity of the hybrid catalyst, maintaining high catalyst utilization at high loading. In standard electrochemical tests, the Mo3S13-SrGO catalyst exhibits a Tafel slope of about 40 mV per decade and a current density of 10 mA cm−2 at 174 mV overpotential, which are significantly better than those exhibited by unsupported [Mo3S13]2− clusters with a Tafel slope of 53 mV per decade and an overpotential of 244 mV at 10 mA cm−2. Further, the hybrid catalyst exhibits a good working stability in acidic media. In the form of nanostructured powder, Mo3S13-SrGO can be readily processed into porous electrodes for practical applications using standard manufacturing technologies.
CRIS-Team Scopus Importer:2023-03-29
Keywords: hydrogen evolution reaction; molybdenum sulfide; noble metal free catalyst; sulfur doped reduced graphene oxide; water electrolysis

Multiscale Tomography-Based Analysis of Polymer Electrolyte Fuel Cells: Towards a Fully Resolved Gas Diffusion Electrode Reconstruction - Klingele, Matthias; Moroni, Riko; Vierrath, Severin; Thiele, Simon (Journal of Electrochemical Energy Conversion and Storage, 2018)
The microstructure of a fuel cell electrode largely determines the performance of the whole fuel cell system. In this regard, tomographic imaging is a valuable tool for the understanding and control of the electrode morphology. The distribution of pore- A nd feature-sizes within fuel cell electrodes covers several orders of magnitude, ranging from millimeters in the gas diffusion layer (GDL) down to few nanometers in the catalyst layer. This obligates the application of various tomographic methods for imaging every aspect of a fuel cell. This perspective evaluates the capabilities, limits, and challenges of each of these methods. Further, it highlights and suggests efforts toward the integration of multiple tomographic methods into single multiscale datasets, a venture which aims at large-scale, and morphologically fully resolved fuel cell reconstructions.
CRIS-Team Scopus Importer:2023-03-29

On the Correlation between the Oxygen in Hydrogen Content and the Catalytic Activity of Cathode Catalysts in PEM Water Electrolysis - Martin, Agate; Trinke, Patrick; Van Pham, Chuyen; Buehler, Melanie; Bierling, Markus; Holzapfel, Peter K. R.; Bensmann, Boris; Thiele, Simon; Hanke-Rauschenbach, Richard (Journal of The Electrochemical Society, 2021)
Altogether five platinum group metal (PGM) and PGM-free cathode catalysts were investigated in full PEM water electrolysis cells regarding their polarisation behaviour and their hydrogen and oxygen recombination properties. It was shown that the recombination activity of permeated oxygen and evolved hydrogen within the cathodic catalyst layer correlates with the activity of the oxygen reduction reaction (ORR) which was determined ex situ with linear sweep voltammetry. We found that the investigated PGM-free cathode catalysts had a low activity for the ORR resulting in higher measurable oxygen in hydrogen volume fractions compared to the PGM catalysts, which are more active for the ORR. Out of the three investigated PGM-free catalysts, only one commercially available material based on a Ti suboxide showed a similar good polarisation behaviour as the state of the art cathode catalyst platinum, while its recombination activity was the lowest of all catalysts. In addition to the recombination of hydrogen and oxygen on the electrocatalysts, we found that the prevalent carbon-based cathodic porous transport layers (PTL) also offer catalytically active recombination sites. In comparison to an inactive PTL, the measurable oxygen flux using carbon-based PTLs was lower and the recombination was enhanced by microporous coatings with high surface areas.
CRIS-Team WoS Importer:2021-12-03

On the effect of anion exchange ionomer binders in bipolar electrode membrane interface water electrolysis - Mayerhoefer, Britta; Ehelebe, Konrad; Speck, Florian D.; Bierling, Markus; Bender, Johannes; Kerres, Jochen A.; Mayrhofer, Karl J. J.; Cherevko, Serhiy; Peach, Retha; Thiele, Simon (Journal of Materials Chemistry A, 2021)
Bipolar membrane|electrode interface water electrolyzers (BPEMWE) were found to outperform a proton exchange membrane (PEM) water electrolyzer reference in a similar membrane electrode assembly (MEA) design based on individual porous transport electrodes (PTE) and a free-standing membrane. We present a detailed study on bipolar interfaces between anion exchange ionomer (AEI) based anode catalyst layers in direct contact with a PEM aiming to unravel influences of local pH, the water splitting bipolar interface and catalyst layer structure. It is conventionally accepted that AEIs used in anion exchange- and bipolar membrane water electrolysis conduct hydroxide anions and ensure a high pH environment in the catalyst layer. We have investigated the effect of different ionomers on the local pH at a metal surface and found a strong correlation with the pH of the surrounding solution rather than the ionomer type. Thus, solely the use of an AEI cannot maintain high pH. A study on BPEMWEs revealed strong indications for the co-existence of a water dissociating bipolar interface, and an acidic oxygen evolution mechanism. The superior performance compared to a PTE-based PEM water electrolyzer seems to stem from reduced contact resistances due to adhesive effects between the oppositely charged polymers. Our study shows that the bipolar approach can be utilized to make PTE-based electrolyzers competitive to commonly employed catalyst coated membranes.
CRIS-Team WoS Importer:2021-06-04

On the limitations in assessing stability of oxygen evolution catalysts using aqueous model electrochemical cells - Knöppel, Julius; Möckl, Maximilian; Escalera-López, Daniel; Stojanovski, Kevin; Bierling, Markus; Böhm, Thomas; Thiele, Simon; Rzepka, Matthias; Cherevko, Serhiy (Nature Communications, 2021)
Recent research indicates a severe discrepancy between oxygen evolution reaction catalysts dissolution in aqueous model systems and membrane electrode assemblies. This questions the relevance of the widespread aqueous testing for real world application. In this study, we aim to determine the processes responsible for the dissolution discrepancy. Experimental parameters known to diverge in both systems are individually tested for their influence on dissolution of an Ir-based catalyst. Ir dissolution is studied in an aqueous model system, a scanning flow cell coupled to an inductively coupled plasma mass spectrometer. Real dissolution rates of the Ir OER catalyst in membrane electrode assemblies are measured with a specifically developed, dedicated setup. Overestimated acidity in the anode catalyst layer and stabilization over time in real devices are proposed as main contributors to the dissolution discrepancy. The results shown here lead to clear guidelines for anode electrocatalyst testing parameters to resemble realistic electrolyzer operating conditions.
CRIS-Team Scopus Importer:2021-04-30

Optimization of anodic porous transport electrodes for proton exchange membrane water electrolyzers - Bühler, Melanie; Hegge, Friedemann; Holzapfel, Peter; Bierling, Markus; Suermann, Michel; Vierrath, Severin; Thiele, Simon (Journal of Materials Chemistry A, 2019)
In this study we investigate the potential of porous transport electrode (PTE) based membrane electrode assemblies (MEAs) for proton exchange membrane water electrolysis. The focus is on the overpotential determining anodic PTE for the oxygen evolution reaction. The influences of catalyst loading, ionomer content and porous titanium substrate on the polarization behavior are analyzed. The comparison of a porous fiber-sintered substrate with a powder-sintered substrate shows no significant differences in the kinetic and mass transport regions. Ohmic losses, however, are lower for fiber PTEs above a catalyst loading of 1.0 mgIrO2 cm-2. Variations of the Nafion content in the catalyst layer reveal changes of mass transport and ohmic losses and have an influence on the reproducibility. Varying the noble metal loading and therefore the thickness of the applied catalyst layer influences the kinetic region and ohmic resistance of the MEAs. The best compromise between reproducibility and performance is found for a loading of 1.4 mgIrO2 cm-2 and 9 wt% Nafion. The stable operation of the aforementioned PTE is shown in a 200 h durability test at 2 A cm-2.
CRIS-Team Scopus Importer:2019-12-17

Oxygen Reduction Reaction in Alkaline Media Causes Iron Leaching from Fe-N-C Electrocatalysts - Ku, Yu-Ping; Ehelebe, Konrad; Hutzler, Andreas; Bierling, Markus; Boehm, Thomas; Zitolo, Andrea; Vorokhta, Mykhailo; Bibent, Nicolas; Speck, Florian D.; Seeberger, Dominik; Khalakhan, Ivan; Mayrhofer, Karl J. J.; et al. (Journal of the American Chemical Society, 2022)
The electrochemical activity of modern Fe-N-C electrocatalysts in alkaline media is on par with that of platinum. For successful application in fuel cells (FCs), however, also high durability and longevity must be demonstrated. Currently, a limited understanding of degradation pathways, especially under operando conditions, hinders the design and synthesis of simultaneously active and stable Fe-N-C electrocatalysts. In this work, using a gas diffusion electrode half-cell coupled with inductively coupled plasma mass spectrometry setup, Fe dissolution is studied under conditions close to those in FCs, that is, with a porous catalyst layer (CL) and at current densities up to -125 mA.cm(-2). Varying the rate of the oxygen reduction reaction (ORR), we show a remarkable linear correlation between the Faradaic charge passed through the electrode and the amount of Fe dissolved from the electrode. This finding is rationalized assuming that oxygen reduction and Fe dissolution reactions are interlinked, likely through a common intermediate formed during the Fe redox transitions in Fe species involved in the ORR, such as FeNxCy and Fe3C@N-C. Moreover, such a linear correlation allows the application of a simple metric-S-number-to report the material's stability. Hence, in the current work, a powerful tool for a more applied stability screening of different electrocatalysts is introduced, which allows on the one hand fast performance investigations under more realistic conditions, and on the other hand a more advanced mechanistic understanding of Fe-N-C degradation in CLs.
CRIS-Team WoS Importer:2022-06-24

Performance of Quaternized Polybenzimidazole-Cross-Linked Poly(vinylbenzyl chloride) Membranes in HT-PEMFCs - Arslan, Funda; Chuluunbandi, Khajidkhand; Freiberg, Anna T.S.; Kormanyos, Attila; Sit, Ferit; Cherevko, Serhiy; Kerres, Jochen; Thiele, Simon; Böhm, Thomas (ACS Applied Materials and Interfaces, 2021)
High-temperature proton-exchange membrane fuel cells (HT-PEMFCs) are mostly based on acid-doped membranes composed of polybenzimidazole (PBI). A severe drawback of acid-doped membranes is the deterioration of mechanical properties upon increasing acid-doping levels. Cross-linking of different polymers is a way to mitigate stability issues. In this study, a new ion-pair-coordinated membrane (IPM) system with quaternary ammonium groups for the application in HT-PEMFCs is introduced. PBI cross-linked with poly(vinylbenzyl chloride) and quaternized with three amines (DABCO, quinuclidine, and quinuclidinol) are manufactured and compared to the state-of-the-art commercial Dapazol PBI membrane ex situ as well as by evaluating their HT-PEMFC performance. The IPMs show reduced swelling and better mechanical properties upon doping, which enables a reduction in membrane thickness while maintaining a comparably low gas crossover and mechanical stability. The HT-PEMFC based on the best-performing IPM reaches up to 530 mW cm-2 at 180 °C under H2/air conditions at ambient pressure, while Dapazol is limited to less than 430 mW cm-2 at equal parameters. This new IPM system requires less acid doping than conventional PBI membranes while outperforming conventional PBI membranes, which renders these new membranes promising candidates for application in HT-PEMFCs.
CRIS-Team Scopus Importer:2021-12-24
Keywords: high-temperature proton-exchange membrane fuel cell; hydrogen gas crossover; ion pair; phosphoric acid; Proton-exchange membrane; quaternary ammonium groups

Photocorrosion of WO3 Photoanodes in Different Electrolytes - Knöppel, Julius; Kormanyos, Attila; Mayerhöfer, Britta; Hofer, André; Bierling, Markus; Bachmann, Julien; Thiele, Simon; Cherevko, Serhiy (ACS Physical Chemistry Au, 2021)
Photocorrosion of an n-type semiconductor is anticipated to be unfavorable if its decomposition potential is situated below its valence band-edge position. Tungsten trioxide (WO3) is generally considered as a stable photoanode for different photoelectrochemical (PEC) applications. Such oversimplified considerations ignore reactions with electrolytes added to the solvent. Moreover, kinetic effects are neglected. The fallacy of such approaches has been demonstrated in our previous study dealing with WO3 instability in H2SO4. In this work, in order to understand parameters influencing WO3 photocorrosion and to identify more suitable reaction environments, H2SO4, HClO4, HNO3, CH3O3SH, as electrolytes are considered. Model WO3 thin films are fabricated with a spray-coating process. Photoactivity of the samples is determined with a photoelectrochemical scanning flow cell. Photostability is measured in real time by coupling an inductively coupled plasma mass spectrometer to the scanning flow cell to determine the photoanode dissolution products. It is found that the photoactivity of the WO3 films increases as HNO3 < HClO4 ≈ H2SO4 < CH3O3SH, whereas the photostability exhibits the opposite trend. The differences observed in photocorrosion are explained considering stability of the electrolytes toward decomposition. This work demonstrates that electrolytes and their reactive intermediates clearly influence the photostability of photoelectrodes. Thus, the careful selection of the photoelectrode/electrolyte combination is of crucial importance in the design of a stable photoelectrochemical water-splitting device.
Keywords: Photocorrosion; Tungsten oxide; Photostability; Water splitting; Electrode kinetics

Photodeposition-Based Synthesis of TiO2@IrOx Core–Shell Catalyst for Proton Exchange Membrane Water Electrolysis with Low Iridium Loading - Hoffmeister, Darius; Finger, Selina; Fiedler, Lena; Ma, Tien Ching; Körner, Andreas; Zlatar, Matej; Fritsch, Birk; Bodnar, Kerstin Witte; Carl, Simon; Götz, Alexander; Zubiri, Benjamin Apeleo; Will, Johannes; et al. (Advanced Science, 2024)
The widespread application of green hydrogen production technologies requires cost reduction of crucial elements. To achieve this, a viable pathway to reduce the iridium loading in proton exchange membrane water electrolysis (PEMWE) is explored. Herein, a scalable synthesis method based on a photodeposition process for a TiO2@IrOx core–shell catalyst with a reduced iridium content as low as 40 wt.% is presented. Using this synthesis method, titania support particles homogeneously coated with a thin iridium oxide shell of only 2.1 ± 0.4 nm are obtained. The catalyst exhibits not only high ex situ activity, but also decent stability compared to commercially available catalysts. Furthermore, the unique core–shell structure provides a threefold increased electrical powder conductivity compared to structures without the shell. In addition, the low iridium content facilitates the fabrication of sufficiently thick catalyst layers at decreased iridium loadings mitigating the impact of crack formation in the catalyst layer during PEMWE operation. It is demonstrated that the novel TiO2@IrOx core–shell catalyst clearly outperforms the commercial reference in single-cell tests with an iridium loading below 0.3 mgIr cm−2 exhibiting a superior iridium-specific power density of 17.9 kW gIr−1 compared to 10.4 kW gIr−1 for the commercial reference.
CRIS-Team Scopus Importer:2024-06-21
Keywords: core–shell catalyst; iridium utilization; low loading; proton exchange membrane water electrolysis; thickness factor

Platinum Dissolution in Realistic Fuel Cell Catalyst Layers - Ehelebe, Konrad; Knöppel, Julius; Bierling, Markus; Mayerhöfer, Britta; Böhm, Thomas; Kulyk, Nadiia; Thiele, Simon; Mayrhofer, Karl; Cherevko, Serhiy (Angewandte Chemie International Edition, 2021)
Pt dissolution has already been intensively studied in aqueous model systems and many mechanistic insights have been gained. Nevertheless, transfer of new knowledge to real-world fuel cell systems is still a significant challenge. To close this gap, we present a novel in situ method combining a gas diffusion electrode (GDE) half-cell with inductively coupled plasma mass spectrometry (ICP-MS). With this setup, Pt dissolution in realistic catalyst layers and the transport of dissolved Pt species through Nafion membranes were evaluated directly. We observed that 1) specific Pt dissolution increased significantly with decreasing Pt loading, 2) in comparison to experiments on aqueous model systems with flow cells, the measured dissolution in GDE experiments was considerably lower, and 3) by adding a membrane onto the catalyst layer, Pt dissolution was reduced even further. All these phenomena are attributed to the varying mass transport conditions of dissolved Pt species, influencing re-deposition and equilibrium potential.
CRIS-Team WoS Importer:2021-03-12

Quantitative synchrotron X-ray tomography of the material-tissue interface in rat cortex implanted with neural probes - Böhm, Thomas; Joseph, Kevin; Kirsch, Matthias; Moroni, Riko; Hilger, André; Osenberg, Markus; Manke, Ingo; Johnston, Midori; Stieglitz, Thomas; Hofmann, Ulrich G.; Haas, Carola A.; Thiele, Simon (Scientific Reports, 2019)
Neural probes provide many options for neuroscientific research and medical purposes. However, these implantable micro devices are not functionally stable over time due to host-probe interactions. Thus, reliable high-resolution characterization methods are required to understand local tissue changes upon implantation. In this work, synchrotron X-ray tomography is employed for the first time to image the interface between brain tissue and an implanted neural probe, showing that this 3D imaging method is capable of resolving probe and surrounding tissue at a resolution of about 1 micrometer. Unstained tissue provides sufficient contrast to identify electrode sites on the probe, cells, and blood vessels within tomograms. Exemplarily, we show that it is possible to quantify characteristics of the interaction region between probe and tissue, like the blood supply system. Our first-time study demonstrates a way for simultaneous 3D investigation of brain tissue with implanted probe, providing information beyond what was hitherto possible.
CRIS-Team Scopus Importer:2019-06-04

Serial section Raman tomography with 10 times higher depth resolution than confocal Raman microscopy - Böhm, Thomas; Moroni, Riko; Thiele, Simon (Journal of Raman Spectroscopy, 2020)
Confocal Raman microscopy enables 3D imaging of various samples solely based on chemical contrast. However, optical artifacts impair resolution and image quality in subsurface imaging. With serial section Raman tomography, we show that serial ultrathin and semithin sectioning by ultramicrotomy can successfully be combined with subsequent confocal Raman imaging. This new 3D Raman imaging technique reaches a depth resolution of up to 100 nm, which is about 10-fold better than in confocal Raman microscopy. Structurally complex and optically inhomogeneous samples can not only be imaged, but also be used to quantify structural parameters. Serial section Raman tomography is a promising method for materials science and possibly also for life sciences.
CRIS-Team Scopus Importer:2020-03-31
Keywords: 3D reconstruction; polymer; Raman imaging; serial sectioning; tomography

Simple fabrication of 12 μm thin nanocomposite fuel cell membranes by direct electrospinning and printing - Breitwieser, Matthias; Klose, Carolin; Klingele, Matthias; Hartmann, Armin; Erben, Johannes; Cho, Hyeongrae; Kerres, Jochen; Zengerle, Roland; Thiele, Simon (Journal of Power Sources, 2017)
Direct membrane deposition (DMD) was recently introduced as a novel polymer electrolyte membrane fabrication method. Here, this approach is extended to fabricate 12 μm thin nanocomposite fuel cell membranes. Poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) nanofibers are directly electrospun onto gas diffusion electrodes. By inkjet-printing Nafion ionomer dispersion into the pore space of PVDF-HFP nanofiber mats, composite membranes of 12 μm thickness were fabricated. At 120 °C and 35% relative humidity, stoichiometric 1.5/2.5 H2/air flow and atmospheric pressure, the power density of the DMD fuel cell (0.19 W cm-2), was about 1.7 times higher than that of the reference fuel cell (0.11 W cm-2) with Nafion HP membrane and identical catalyst. A lower ionic resistance and, especially at 120 °C, a reduced charge transfer resistance is found compared to the Nafion HP membrane. A 100 h accelerated stress test revealed a voltage decay of below 0.8 mV h-1, which is in the range of literature values for significantly thicker reinforced membranes. Finally, this novel fabrication approach enables new degrees of freedom in the design of complex composite membranes. The presented combination of scalable deposition techniques has the potential to simplify and thus reduce cost of composite membrane fabrication at a larger scale.
CRIS-Team Scopus Importer:2023-03-29
Keywords: Composite membrane; Direct membrane deposition; Electrospinning; Inkjet-printing; PEMFC

Spatially and temporally resolved monitoring of doping polybenzimidazole membranes with phosphoric acid - Arslan, Funda; Böhm, Thomas; Kerres, Jochen; Thiele, Simon (Journal of Membrane Science, 2021)
Polybenzimidazole-based membranes in high temperature proton exchange membrane fuel cells require doping with phosphoric acid to enable proton conductivity. The level of phosphoric acid doping is traditionally determined by titration or weighing, but these methods only provide limited information, since they do not offer spatial resolution. We show that confocal Raman microscopy can not only provide information on the level of doping, but in addition about the spatial distribution of the dopant. We prove that doping is a diffusion-limited process, leading to a spatially inhomogeneous distribution of phosphoric acid unless doping is performed to saturation. Further, evidence of a slow redistribution of the dopant within a freestanding membrane under ambient conditions is provided. Confocal Raman microscopy can be used as a non-invasive measurement tool to investigate status and progress of doping a membrane with phosphoric acid.
CRIS-Team Scopus Importer:2021-02-26
Keywords: Acid doping level (ADL); Acid uptake (AU); Fuel cells (FCs); High temperature (HT); Phosphoric acid (PA); Polybenzimidazole (PBI); Polymer electrolyte membrane; Raman spectroscopy

Spatially Resolved Quantification of Ionomer Degradation in Fuel Cells by Confocal Raman Microscopy - Boehm, Thomas; Moroni, Riko; Breitwieser, Matthias; Thiele, Simon; Vierrath, Severin (Journal of The Electrochemical Society, 2019)
Ionomer membranes are crucial components ofmany electrochemical devices. In this work, confocal Ramanmicroscopy is employed to characterize Nafion ionomers quantitatively in pristine status and after usage as a proton exchange membrane in a fuel cell. Confocal Raman microscopy allows non-destructive thickness and equivalent weight measurements of Nafion with a 95% confidence interval of +/- 13 g mol(-1) at an equivalent weight of 1000 g mol(-1), which is significantly more accurate than previously reported methods. Characterization can be performed at a spatial resolution better than 2 mu m, providing insights into local membrane degradation after fuel cell operation. Membrane thinning to less than 40% of the initial thickness of Nafion NR-211 occurs after a 100 h open circuit voltage hold, accompanied by an anisotropic increase of the equivalent weight from 1035 g mol(-1) to an average of 1200 g mol(-1). Most pronounced increases are found close to the anode. Further, the characterization of a Nafion XL membrane shows that its microporous reinforcement is represented as increased equivalent weight with local heterogeneities within the membrane. These results show that confocal Raman microscopy is a valuable tool to investigate ionomers that are used as ion exchange membranes in electrochemical devices. (c) The Author(s) 2019. Published by ECS.
CRIS-Team WoS Importer:2019-03-15

Stabilization of Li-S batteries with a lean electrolyte: Via ion-exchange trapping of lithium polysulfides using a cationic, polybenzimidazolium binder - Pham, Chuyen Van; Liu, Lili; Britton, Benjamin; Walter, Michael; Holdcroft, Steven; Thiele, Simon (Sustainable Energy & Fuels, 2020)
Implementing Li-S cells using high S loading and lean electrolyte content is considered the only viable way to achieve competitive specific energy for practical applications. However, under these conditions, the cell cycle life and performance are drastically reduced due to the severe polysulfide shuttle effect, electrolyte depletion, and sluggish electrochemical S conversion. Here we demonstrate that a cationic polymer binder can efficiently mitigate the polysulfide shuttle effect. The employed cationic polymer, poly[2,2′-(2,2′′,4,4′′,6,6′′-hexamethyl-p-terphenyl-3,3′′-diyl)-5,5′-bibenzimidazolium iodide] (HMT-PMBI(I-)), possesses abundant benzimidazolium cations which interact with dissolved polysulfide anions when used as an active binder. Simultaneously, density functional theory calculations show that HMT-PMBI+ loosely binds with TFSI- and Li+, allowing HMT-PMBI(I-) to exchange its I- anion with TFSI- from the electrolyte salt to form HMT-PMBI(TFSI) containing loosely bound Li+. This forms a Li+ conducting phase within the cathode, allowing a reduced electrolyte content. Therefore, the novel active binder enables a stable cyclability of >440 cycles for Li-S batteries with relatively high S-loading (3-4 mg cm-2) and a lean electrolyte content of 6 μl mgS-1. As the cells prepared in this work use inexpensive, commercially available materials and a conventional doctor-blade fabrication approach, the results are highly relevant to practical applications.
CRIS-Team Scopus Importer:2020-03-27

Study of the Mechanisms of Internal Short Circuit in a Li/Li Cell by Synchrotron X-ray Phase Contrast Tomography - Sun, Fu; Moroni, Riko; Dong, Kang; Markeotter, Henning; Zhou, Dong; Hilger, Andre; Zielke, Lukas; Zengerle, Roland; Thiele, Simon; Banhart, John; Manke, Ingo (ACS Energy Letters, 2017)
Knowledge about degradation and failure of Li-ion batteries (LIBs) is of paramount importance, especially because failure can be accompanied by severe hazards. To contribute to the understanding of such phenomena, synchrotron in-line phase contrast X-ray tomography was employed to investigate internal cell deformation and degradation caused by an internal short circuit (ISC). The tomographic images taken from an uncycled Li/Li cell and a short-circuited Li/Li cell reveal how lithium microstructures (LmSs) develop during electrochemical stripping and plating during discharge and charge and how the three-layer separator used is damaged by growing LmSs and delaminates and melts as a consequence of an ISC. Previously unknown insights into the internal cell degradation and deformation mechanisms caused by an ISC are obtained and provide hints of how the properties of the separator could be modified to improve the reliability and safety of current- and next-generation LIBs.
CRIS-Team Scopus Importer:2023-03-29

Sulfur doped reduced graphene oxide as metal-free catalyst for the oxygen reduction reaction in anion and proton exchange fuel cells - Klingele, Matthias; Chuyen Pham; Vuyyuru, Koteswara Rao; Britton, Benjamin; Holdcroft, Steven; Fischer, Anna; Thiele, Simon (Electrochemistry Communications, 2017)
Sulfur doped reduced graphene oxide (S-rGO) is investigated for catalytic activity towards the oxygen reduction reaction (ORR) in acidic and alkaline electrolytes. X-ray photoelectron spectroscopy shows that sulfur in S-rGO is predominantly integrated as thiophene motifs within graphene sheets. The overall sulfur content is determined to be approximately 2.2 at.% (elemental analysis). The catalytic activity of S-rGO towards the ORR is investigated by both rotating disc electrode (RDE) and polymer electrolyte fuel cell (PEFC) measurements. RDE measurements reveal onset potentials of 0.3 V and 0.74 V (vs. RHE) in acidic and alkaline electrolyte, respectively. In a solid electrolyte fuel cell with S-rGO as cathode material, this is reflected in an open circuit voltage of 0.37 V and 0.78 V and a maximum power density of 1.19 mW/cm2 and 2.38 mW/cm2 in acidic and alkaline polymer electrolyte, respectively. This is the first report investigating the catalytic activity of a sulfur doped carbon material in both acidic and alkaline liquid electrolyte, as well as in both proton and anion exchange polymer electrolyte fuel cells.
CRIS-Team Scopus Importer:2023-03-29
Keywords: Carbon; Catalysis; Fuel cells; Oxygen reduction reaction; Sulfur doped graphene

Tailoring the Membrane-Electrode Interface in PEM Fuel Cells: A Review and Perspective on Novel Engineering Approaches - Breitwieser, Matthias; Klingele, Matthias; Vierrath, Severin; Zengerle, Roland; Thiele, Simon (Advanced Energy Materials, 2018)
The interface between the catalyst layer (CL) and the polymer electrolyte membrane (PEM) in a fuel cell has substantial impact on its electrochemical performance. In consequence, there have been growing research activities to engineer this interface to improve the performance of polymer electrolyte membrane fuel cells (PEMFCs). This review summarizes these novel approaches and compares the various techniques. Based on available fuel cell data in the literature, a quantitative comparison of relative improvements due to a micro- and nano-engineered PEM|CL interface is provided. This allows several conclusions: First, regardless of the applied method, a re-engineering of the PEM|CL interface leads to an improvement of power-determining parameters, such as mass transport resistances. The latter has hitherto not been clearly connected to the PEM|CL interface and is an important piece of information for future fuel cell development. Second, for patterned membrane surfaces, feature sizes of about 1–10 µm on the membrane surface seem to result in the most significant power density improvement. Third, an engineered PEMCL interface can contribute to extend the fuel cell durability due to enhanced adhesion and contact between the two layers. With this, novel membrane electrode assemblies (MEAs) can be designed that enable significantly higher power densities compared conventional 2D-layer MEAs.
CRIS-Team Scopus Importer:2023-03-29
Keywords: fuel cells; interface engineering; PEM/CL interfaces; PEMFC

The 2-Propanol Fuel Cell: A Review from the Perspective of a Hydrogen Energy Economy - Brodt, Matthew; Mueller, Karsten; Kerres, Jochen; Katsounaros, Ioannis; Mayrhofer, Karl; Preuster, Patrick; Wasserscheid, Peter; Thiele, Simon (Energy Technology, 2021)
The 2-propanol fuel cell has been shown to hold several key advantages over the more established methanol fuel cell, including a comparably high real open-circuit voltage, reduced fuel crossover through a Nafion membrane and a benign toxicological fuel profile. In addition, while the highly selective partial oxidation of 2-propanol to acetone in a fuel cell (rather than the more typical complete combustion of organic fuels to CO2) has been viewed as a disadvantage in the past, recent work has shown that the 2-propanol/acetone couple is compatible with traditional hydrocarbon liquid organic hydrogen carrier (LOHC) systems though transfer hydrogenation. With this approach, a disadvantage of hydrogen LOHC logistics—the steep energy cost of dehydrogenation that must be provided during energy-lean times—can be largely avoided. This LOHC compatibility along with the potential for high fuel-cell performance could place the 2-propanol fuel cell (also referred to as the direct isopropanol fuel cell or DIFC) in a position to enable a hydrogen energy economy while avoiding the drawbacks of molecular hydrogen transport and storage. In this Review, the purpose is to ascertain the state-of-the-art of DIFCs—an understudied yet promising research area with unique advantages and challenges.
CRIS-Team Scopus Importer:2021-07-30
Keywords: 2-propanol fuel cells; direct isopropanol fuel cells; liquid organic hydrogen carriers

The influence of acetone and isopropanol crossover on the direct isopropanol fuel cell - Venus, Dominik; Valeske, Moritz; Brodt, Matthew; Wasserscheid, Peter; Thiele, Simon (Electrochemistry Communications, 2024)
Liquid organic hydrogen carriers (LOHC) offer a promising option to store and release hydrogen on demand within existing infrastructure. The direct isopropanol fuel cell (DIFC) uses the electrochemical acetone/isopropanol LOHC couple and combines the advantages of high fuel energy density at ambient conditions with CO2-free direct electricity production. Like other alcohol fuel cells, the DIFC combines two kinetically slow reactions, the isopropanol oxidation reaction (IOR) and the oxygen reduction reaction (ORR), requiring considerable overpotentials to drive the reactions. Accordingly, deconvoluting kinetic characteristics in the full cell is difficult. Therefore, this work uses the electrolytic electrochemical dehydrogenation unit (EDU), consisting of the IOR and the kinetically fast hydrogen evolution reaction in acidic media. This EDU then serves as an IOR full-cell model to get insights on the DIFC. Correspondingly, the demonstrated work is a comparison study investigating in-house fabricated catalyst-coated membrane electrode assemblies as hydrogen fuel cells, DIFC, and EDU. It investigates characteristic features of the DIFC and demonstrates how the acetone and isopropanol crossover affect the cathode of the DIFC.
CRIS-Team Scopus Importer:2024-11-01
Keywords: Direct alcohol fuel cell (DAFC); Direct isopropanol fuel cell (DIFC); Electro-oxidation of alcohols; Electrochemical addressable LOHC (EC-LOHC); Liquid organic hydrogen carriers (LOHC)

The influence of intrinsically proton conductive electrode binder materials on HT-PEMFC performance - Arslan, Funda; Dirsch, Jens; Wagner, Maximilian; Freiberg, Anna; Komma, Miriam; Kerres, Jochen; Thiele, Simon; Böhm, Thomas (Journal of Power Sources, 2023)
High temperature proton exchange membrane fuel cells (HT-PEMFCs) typically employ either acid-absorbing or hydrophobic electrode binders in their catalyst layers (CLs). A recently introduced alternative is the ionomeric binder PWN, poly(2,3,5,6-tetrafluorostyrene-4-phosphonic acid). In literature, PWN with a phosphonation degree of 70% was shown to remarkably improve HT-PEMFC performance. Here, we investigate the influence of the phosphonation degree (40–95%) of this ionomeric binder on HT-PEMFC performance. PWN is employed in the cathode CL and compared to the commonly used polytetrafluoroethylene (PTFE) binder. The electrochemical behavior is tested at 180 °C at ambient pressure under H2/air conditions using a commercial phosphoric acid (PA)-doped PBI-membrane. HT-PEMFCs with PWN generally outperform fuel cells (FCs) with PTFE after a full break-in regarding peak power density (PPD), activation overpotential (as studied by Tafel analysis), and reproducibility in the mass transport region. Further, PWN-electrodes show higher electrochemically active surface areas (ECSAs) than PTFE-electrodes after completing the break-in. We find that the phosphonation degree has a substantial impact on the PPD, with PWNs with lower phosphonation degrees (40–60%) outperforming highly phosphonated PWNs (70–95%). Taken together, PWN as an ionomeric electrode binder in HT-PEMFCs shows remarkable improvements in performance, but a precise adjustment of the phosphonation degree is required to obtain optimal results.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Binder; Fuel cell; High temperature; Ionomer; Phosphoric acid; Proton exchange membrane; PWN

The influence of the anion exchange membrane on mass-transport limiting phenomena in bipolar interface fuel cells with Fe-N/C based cathode catalyst layers - Seeberger, Dominik; Hauenstein, Pascal; Hartert, Adrian; Thiele, Simon (RSC Advances, 2021)
Water management is a very important issue in low temperature fuel cells such as proton exchange membrane fuel cells (PEMFCs) or anion exchange membrane fuel cells. Within bipolar interface fuel cells, water management inhibits an even more critical role. The earlier work on bipolar interface fuel cells (BPIFCs), employing Fe-N/C on the cathode side for the oxygen reduction reaction (ORR) in an alkaline environment, demonstrated increased stability of the catalyst compared to the acidic environment of the conventional PEMFCs. However, for the BPIFCs, severe mass transport limitations (MTL) dramatically reduced the power output of the cell within a few hours. In the present work water transport processes are identified as the source of the observed MTL, after evaluating the performance data of BPIFCs, where the amount of directly deposited anion exchange membrane (AEM) material was varied. It can be seen that the BPIFCs with lower AEM content show an earlier onset of MTL than the cells prepared with higher AEM content. It is shown that the AEM can be used as a tool to regulate the influx rate of product water from the bipolar interface into the CCL and that flooding of the porous layers is identified as the main source of the observed MTL. This work paves the way for further development of BPIFCs using Fe-N/C at the cathode electrode, as novel cell design strategies can now focus exclusively on avoiding flooding phenomena.
CRIS-Team WoS Importer:2021-11-19

Three-dimensional microstructure analysis of a polymer electrolyte membrane water electrolyzer anode - Hegge, Friedemann; Moroni, Riko; Trinke, Patrick; Bensmann, Boris; Hanke-Rauschenbach, Richard; Thiele, Simon; Vierrath, Severin (Journal of Power Sources, 2018)
The anode catalyst layer of a PEM water electrolyzer is reconstructed using a combination of FIB-SEM tomography and ionomer modeling. The pore space is infiltrated with silicone, enabling good discrimination between pores and IrRuOx catalyst material, while the ionomer cannot be imaged. The reconstructed volume of 29 μm × 24 μm x 7 μm contains catalyst particles with a median size of 0.5 μm and has a porosity of 55%. By modeling different ionomer contents inside the pore space, the impact on microstructural and transport parameters is investigated. At an ionomer content of 40-50% of the pore volume, all transport parameters are in a reasonable range, confirming experimental results from literature. At an ionomer content of 48% the catalyst layer has a porosity of 29%, a median pore size of 0.94 μm, a permeability of the pore space of 1.8mD and a mean ionomer film thickness of 0.4μm. The tortuosities of the ionomer and the pore space are calculated to 3.5 and 6.7 at the corresponding phase fractions of 26% and 29% respectively. The electrochemically active surface area estimated from the tomography (1.0m2g−1) is considerably lower than literature values, indicating a roughness below FIB-SEM resolution.
CRIS-Team Scopus Importer:2023-03-29
Keywords: Catalyst layers; FIB-SEM tomography; Ionomer modeling; Microstructure; PEM water electrolyzers

Tomographic Reconstruction and Analysis of a Silver CO2 Reduction Cathode - Mclaughlin, David; Bierling, Markus; Moroni, Riko; Vogl, Christoph; Schmid, Guenter; Thiele, Simon (Advanced Energy Materials, 2020)
Tomographic reconstruction has been well established as a valuable tool in the analysis of polymer electrolyte fuel cell (PEMFC) electrodes. While forays have been made into applying it to polymer electrolyte water electrolyzer (PEMWE) electrodes, CO2 electrolyzer electrodes are still new ground. Here a tomographic analysis of an electrochemical CO2 reduction gas diffusion electrode by means of focused ion beam scanning electron microscope tomography is presented. The reconstruction shows a porosity of 68%. While most of the porosity is on the nanoscale, a broad tail of micropores is observed in the distribution. The spatial distribution of the pores is nonuniform. The large pores are concentrated in the center of the layer in the through-plane direction. From the reconstruction, an effective diffusivity factor of 0.5 for the catalyst layer is calculated. The Knudsen number of 0.19 obtained from the later shows that the diffusion is mostly in the bulk regime. Flooding of the catalyst layer is likely to decrease the effective diffusivity factor substantially.
CRIS-Team Scopus Importer:2020-04-17
Keywords: CO; FIB-SEM; gas diffusion electrodes; power-to-X technology; tomography

Toward Understanding Catalyst Layer Deposition Processes and Distribution in Anodic Porous Transport Electrodes in Proton Exchange Membrane Water Electrolyzers - Bierling, Markus; McLaughlin, David; Mayerhöfer, Britta; Thiele, Simon (Advanced Energy Materials, 2023)
Finding the optimum structure in porous transport electrodes (PTEs) for proton exchange membrane water electrolyzer anodes is one of the central current technological challenges. Both the structure of the porous transport layer (PTL) and its interaction with the catalyst layer are crucial in finding this optimum structure. In this regard, manufacturing the catalyst layer on top of a PTL as a structure-building process must be understood to find improved transport electrode structures. This work presents a PTE tomography where the catalyst ink is directly processed on a PTL. The catalyst distribution of anodic PTEs is analyzed and compared via X-ray microtomography and cross-sectional imaging of embedded PTE samples. The majority of the catalyst lies within the first 100 µm of the PTE. Considering the penetration depth of the membrane, a maximum of 60% of the catalyst is effectively used. For the first time, a voxel-based catalyst layer deposition model is created and analyzed that is based on simple assumptions in the deposition process. This deposition model fits very well with the previous tomographic analysis. In the future, this model will allow more profound insight into the manufacturing process and is an important prerequisite for a future optimum design of PTEs.
CRIS-Team Scopus Importer:2023-03-03
Keywords: catalyst distributions; gas diffusion electrodes; modeling; PEM water electrolysis; porous transport electrodes; tomographies; ultrasonic spray coating

Tridoped Reduced Graphene Oxide as a Metal-Free Catalyst for Oxygen Reduction Reaction Demonstrated in Acidic and Alkaline Polymer Electrolyte Fuel Cells - Van Pham, Chuyen; Klingele, Matthias; Britton, Benjamin; Vuyyuru, Koteswara Rao; Unmuessig, Tobias; Holdcroft, Steven; Fischer, Anna; Thiele, Simon (Advanced Sustainable Systems, 2017)
Recently, it has been demonstrated that doping of graphene by elements such as N, S, or F creates active sites for the oxygen reduction reaction (ORR). This results from bond polarization caused by the difference in electronegativity between heteroatom dopants and carbon, and/or the presence of defects within the graphene lattice. In this work, fluorine, nitrogen, and sulfur tridoped reduced graphene oxide (F,N,S-rGO) is designed to combine these catalytically active sites. F,N,S-rGO can be inexpensively synthesized by a facile and scalable route involving pyrolysis at 600 °C of sulfur-doped rGO in the presence of Nafion and dimethyl formamide (DMF). The pyrolysis of Nafion and DMF provides F• and N• radicals which serve as doping agents. Rotating disk electrode investigations reveal the ORR catalytic activities of F,N,S-rGO in both acidic and alkaline media, which are consistent with the real performances of the respective polymer electrolyte fuel cells (PEFCs). Maximum power densities of 14 and 46 mW cm−2 are obtained for the acidic and alkaline PEFCs, respectively, using F,N,S-rGO as ORR catalysts. To the best of knowledge, this is the first report on the synthesis of F,N,S tridoped rGO and on its ORR activity in both acidic and alkaline PEFCs.
CRIS-Team Scopus Importer:2023-03-29
Keywords: fuel cells; metal-free catalysts; oxygen reduction reaction; tridoped graphene

Understanding the activity transport nexus in water and CO2 electrolysis: State of the art, challenges and perspectives - Etzold, Bastian J.M.; Krewer, Ulrike; Thiele, Simon; Dreizler, Andreas; Klemm, Elias; Turek, Thomas (Chemical Engineering Journal, 2021)
This article reviews the challenge of expanding the current research focus on water and CO2 electrolysis from catalyst-related insights towards achieving complete understanding of the activity transport nexus within full electrolysis cells. The challenge arises from the complex interaction of a multitude of phenomena taking place at different scales that span several orders of magnitude. An overview of current research on materials and components, experiments and simulations are provided. As well as obvious differences, there are similar principles and phenomena within water and CO2 electrolysis technologies, which are extracted. Against this background, a perspective on required future research within the individual fields, and the need for a multidisciplinary research approach across natural, materials and engineering sciences to tackle the activity transport nexus is presented.
CRIS-Team Scopus Importer:2021-07-09

Water management in novel direct membrane deposition fuel cells under low humidification - Breitwieser, M.; Moroni, R.; Schock, J.; Schulz, Michael; Schillinger, B.; Pfeiffer, F.; Zengerle, Roland; Thiele, Simon (International Journal of Hydrogen Energy, 2016)
Polymer electrolyte membrane fuel cells (PEMFCs) fabricated by direct membrane deposition (DMD) were shown to work even at dry conditions without significant deterioration of the membrane resistance. Here, in situ neutron radiography is used to investigate the water management in those fuel cells to uncover the phenomena that lead to the robust operation under low humidification. A constant level of humidification within the membrane electrode assembly (MEA) of a DMD fuel cell is observed even under dry anode operation and 15% relative humidity on the cathode side. This proves a pronounced back diffusion of generated water from the cathode side to the anode side through the thin deposited membrane layer. Over the entire range of polarization curves a very high similarity of the water evolution in anode and cathode flow fields is found in spite of different humidification levels. It is shown that the power density of directly deposited membranes in contrast to a 50 μm thick N-112 membrane is only marginally affected by dry operation conditions. Water profiles in through-plane direction of the MEA reveal that the water content in the DMD fuel cell remains steady even at high current densities. This is in contrast to the N-112 reference fuel cell which shows a strong increase in membrane resistance and a reduced MEA water content with raising current densities. Thus this new MEA fabrication technique has a promising perspective, since dry operation conditions are highly requested in order to reduce fuel cell system costs.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Back diffusion; Direct membrane deposition; Neutron radiography; PEMFCs; Water management